Laminated polyester film and method for manufacturing polyester film

JP2022122830A5Active Publication Date: 2024-12-16TORAY INDUSTRIES INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022006252
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-11-29
Filing Date
2022-01-19
Publication Date
2024-12-16
Estimated Expiration
2042-01-19

AI Technical Summary

Technical Problem

The increasing number of multilayer ceramic capacitors (MLCCs) has led to a significant environmental burden due to discarded release films, which are difficult to reuse because their release layers contain incompatible components, and existing methods for reusing these films are inefficient or require extensive processing.

Method used

A laminated polyester film with specific surface energy and thickness conditions, containing a layer with a sulfonate-modified polyvinyl alcohol skeleton, allows for easy removal and reuse by washing, suitable for subsequent processing and reducing environmental impact.

Benefits of technology

The laminated polyester film enables high reusability and suitability for subsequent processes, effectively reducing waste and enhancing the recyclability of release films used in MLCC manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000045_0000
    Figure 00000045_0000
Patent Text Reader

Abstract

To provide a laminated polyester film that has high reusability and is suited for post-process processing.SOLUTION: Provided is a laminated polyester film that has a polyester film and a layer X satisfying the following conditions. Condition 1: 20≤γXP≤45. Condition 2: 3.0≤γXH≤10. γXP(mN / m): polar component of surface free energy of layer X. γXH(mN / m): hydrogen bond component of surface free energy of layer X.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a laminated polyester film that is excellent at removing layers provided in a laminated polyester film. [Background technology]

[0002] While plastics are used in a variety of fields, they are also considered a cause of marine pollution, such as microplastics, making it urgent to reduce the environmental impact of plastics. Furthermore, in recent years, with the evolution of IoT (Internet of Things), the number of electronic devices such as CPUs installed in computers and smartphones has increased dramatically, and consequently, the number of multilayer ceramic capacitors (MLCCs), which are crucial for driving these electronic devices, has also increased explosively. The general manufacturing method for MLCCs involves using a plastic film as a base material, applying a release layer to the base material, laminating ceramic green sheets and electrodes onto the release film, drying and hardening the laminate, peeling the laminate from the release film, laminating multiple layers, and firing. In this process, the release film is discarded as waste material.

[0003] In other words, the recent explosive increase in MLCC production has led to a growing problem of environmental burden due to the increasing amount of release film discarded as waste. The release layer components in the release film used in the MLCC manufacturing process generally have a different composition from the components that make up the film, from the perspective of release properties. Therefore, if release film with the release layer attached is remelted as is, the components of the release layer will be present as foreign matter, making reuse difficult.

[0004] As an example of a technology for reusing release films, Patent Document 1 discloses a method of reusing a release film having a release layer by cleaning it with a metal brush and removing the release layer. Patent Document 2 discloses a method of reusing a film in which a water-soluble resin layer is placed between the release layer and the polyester film, and the release layer is removed by washing with water. Furthermore, Patent Document 3 discloses a method of obtaining a ceramic green sheet with good smoothness and peelability by defining the process conditions when laminating the ceramic green sheet, and in which a water-soluble resin layer is placed between the release layer and the polyester film, and the release layer is removed by washing with water. [Prior art documents] [Patent Documents]

[0005] [Patent Document 1] Japanese Patent Publication No. 2012-171276 [Patent Document 2] Patent No. 4284936 [Patent Document 3] Japanese Patent Publication No. 2004-160773 [Overview of the project] [Problems that the invention aims to solve]

[0006] As mentioned above, with the explosive increase in MLCC production, it is important to reduce the environmental burden caused by the increasing amount of release film discarded as waste. Therefore, the laminated polyester film used as the base material for the release film needs to be "reusable," and the film itself needs to be suitable for subsequent processing.

[0007] In response to the above demands, when the inventors of the present invention examined the aforementioned prior art, in the case of the technology described in Patent Document 1, the release layer could not be uniformly removed, and it took a lot of labor when reused, and there was a problem with reusability. In the case of the technology described in Patent Document 2, the reusability was also insufficient. In addition, in the case of the technology described in Patent Document 3, depending on the process conditions, the post-processing property was poor, and there was also room for improvement in reusability.

[0008] From the above points, an object of the present invention is to provide a laminated polyester film with high reusability and suitable for processing in subsequent processes.

Means for Solving the Problems

[0009] [I] A laminated polyester film having a polyester film and a layer X satisfying the following conditions. Condition 1: 20 ≤ γX P ≤ 45 Condition 2: 3.0 ≤ γX H ≤ 10 γX P (mN / m): Polar component of the surface free energy of layer X γX H (mN / m): Hydrogen bond component of the surface free energy of layer X [II] The laminated polyester film according to [I], wherein the thickness xa (nm) of the layer X and the surface roughness RzjisB (nm) of the surface on the side opposite to the surface (A surface) having the layer X of the polyester film satisfy the following conditions. Condition 3: 1.0 ≤ RzjisB / xa ≤ 20.0 xa (nm): Thickness of layer X [III] The laminated polyester film according to [I] or [II], wherein the layer X satisfies the following conditions. Condition 4: 20 ≤ γX P ≤ 30 Condition 5: 6.0 ≤ γX H ≤ 10 [IV] The laminated polyester film according to [II] or [III], which satisfies the following conditions. Condition 6: 1.5 ≤ RzjisB / xa ≤ 10.0 [V] A laminated polyester film according to any one of [I] to [IV], wherein the thickness xa (nm) of the layer X and the surface roughness RzjisX (nm) of the layer X satisfy the following conditions. Condition 7: 0.01≦RzjisX / xa≦3.0 [VI] A laminated polyester film according to any one of [I] to [V], wherein the thickness xa of the layer X is 10 nm or more and 500 nm or less. [VII] A laminated polyester film according to any one of [I] to [VI], wherein the water contact angles HX(1)(°) and HX(20)(°) of the layer X satisfy the following conditions. Condition 8: 5≦|HX(1)-HX(20)|≦60 HX(1)(°): Contact angle 1 second after water comes into contact with layer X HX(20)(°): Contact angle 20 seconds after water comes into contact with layer X. [VIII] A laminated polyester film according to any one of [I] to [VII], wherein the layer X comprises a resin having a polyvinyl alcohol skeleton. [IX] The laminated polyester film according to [VIII], comprising a resin having a sulfonate-modified polyvinyl alcohol skeleton in the layer X. [X] A laminated polyester film according to any one of [I] to [IX], wherein the degree of crystallinity of the layer X is 14% or more and 40% or less. [XI] The laminated polyester film according to [X], wherein the degree of crystallinity of layer X is greater than 31% and 40% or less. [XII] A laminated polyester film according to any one of [I] to [XI], wherein the layer X contains a resin with a degree of polymerization greater than 200. [XIII] A laminated polyester film according to any one of [I] to [XII], having layer Y, layer X, and polyester film in this order, satisfying the following conditions. Condition 9:80≦HY(1)≦120 Condition 10:1≦|HY(1)-HY(20)|≦90 HY(1)(°): Contact angle 1 second after water comes into contact with layer Y HY(20)(°): Contact angle 20 seconds after water comes into contact with layer Y [XIV] The laminated polyester film according to [XIII], wherein the solvent durability of the surface of the layer Y, determined by the following method, is 5% or more and 100% or less. [Method for measuring solvent durability] Testing machine: Japan Society for the Promotion of Science type testing machine (Type II friction testing machine as described in JIS L 0849 (2013)) Friction element: Cotton cloth (metal cloth No. 3) impregnated with a toluene:ethanol mixed solvent (mass ratio 1:1) Load: 1kg Number of round trips: 30 Solvent durability rate (%) = F(A) / F(B) × 100 F(A): Peeling force on the surface of layer Y F(B): Peeling force on the surface of layer Y after solvent-impregnated cloth abrasion test. [XV] Hydrogen bonding component γY of the surface free energy of the layer Y H A laminated polyester film as described in [XIII] or [XIV], wherein the ratio is 1.5 or more and 10 or less. [XVI] A laminated polyester film according to any one of [XIII] to [XV], wherein a release layer is provided on the surface of layer Y opposite to the surface in contact with layer X, and used for release purposes in which the release layer is peeled off from layer Y. [XVI] A laminated polyester film according to [XVI] used in applications where the release layer is peeled off from layer Y, and then layers X and Y are removed. [XVIII] The laminated polyester film described in [XVII], used for applications that reuse a laminated polyester film from which layers X and Y have been removed. [XIX] The laminated polyester film according to any one of [XVI] to [XVIII], wherein the release layer is a ceramic green sheet mainly composed of barium titanate. [XX] A laminated polyester film according to any one of [I] to [XIX], used at least as part of a release film for the manufacturing process of multilayer ceramic capacitors (MLCCs). [XXI] A laminated polyester film having a layer Y on at least one surface layer that satisfies the following conditions. Condition 11:80≦HY(1)≦120 Condition 12:1≦|HY(1)-HY(20)|≦90 HY(1)(°): Contact angle 1 second after water comes into contact with layer Y HY(20)(°): Contact angle 20 seconds after water comes into contact with layer Y [XXII] The laminated polyester film according to any one of [I] to [XXI], wherein the polyester film has a laminated structure of three or more layers, the layer comprising a layer constituting surface A (A layer) which is one surface of the polyester film, a layer constituting surface B (B layer) which is the other surface, and a layer without a surface (C layer), and the C layer contains recycled polyester raw material. [XXIII] A method for manufacturing a polyester film, comprising using the laminated polyester film described in [XXII], having at least a release layer, layer Y, and polyester film in that order, the steps of peeling the release layer from layer Y, removing layer Y from the film from which the release layer has been peeled off, manufacturing recycled raw materials from the film from which the release layer and layer Y have been removed, and further manufacturing a film using the recycled raw materials. [XXIV] A polyester film in which a layer X mainly composed of a hydrophilic resin is laminated on one side (side A) of the polyester film, wherein the thickness xa (nm) of the layer X and the surface roughness RzjisB (nm) of the side (side B) opposite to the side having layer X (side A) of the polyester film satisfy the following conditions. Condition 13:0.2≦RzjisB / xa≦20.0 [XXV] A laminated polyester film comprising a polyester film and a layer X, wherein layer X contains a resin having a sulfonate-modified polyvinyl alcohol skeleton, the copolymerization amount of the sulfonate-modified polyvinyl alcohol skeleton resin by the sulfonate is 0.1 mol% or more and 10 mol% or less, and when the average degree of polymerization of layer X is determined by the method described in JIS K 6726 (1994), the resulting average degree of polymerization is 200 or more and 2400 or less, and when the degree of saponification of layer X is determined by the method described in JIS K 6726 (1994), the resulting degree of saponification is 30 or more and 97 or less. [Effects of the Invention]

[0010] According to the present invention, it is possible to provide a laminated polyester film that is highly reusable and suitable for processing in subsequent steps. [Modes for carrying out the invention]

[0011] The present invention will be described in detail below with specific examples.

[0012] The present invention relates to a polyester film and a laminated polyester film having one or more layers. The polyester referred to in the present invention is composed of a dicarboxylic acid component and a diol component. In this specification, a component refers to the smallest unit that can be obtained by hydrolysis of the polyester. Examples of dicarboxylic acid components constituting such polyester include aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 1,8-naphthalenedicarboxylic acid, 4,4'-diphenyldicarboxylic acid, and 4,4'-diphenyletherdicarboxylic acid, or their ester derivatives.

[0013] Furthermore, examples of diol components constituting such polyesters include aliphatic diols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,2-butanediol, and 1,3-butanediol; alicyclic diols such as cyclohexanedimethanol and spiroglycol; and polysaccharides in which multiple diols are linked together. Among these, from the viewpoint of mechanical properties and transparency, polyethylene terephthalate (PET), polyethylene-2,6-naphthalenedicarboxylate (PEN), and polyesters copolymerized with isophthalic acid or naphthalenedicarboxylic acid in part of the dicarboxylic acid component of PET, and polyesters copolymerized with cyclohexanedimethanol, spiroglycol, and diethylene glycol in part of the diol component of PET are preferably used.

[0014] A preferred embodiment of the laminated polyester film of the present invention is a laminated polyester film having a polyester film and a layer X that satisfies the following conditions 1 and 2. From the viewpoint of simpler structure and higher productivity, a more preferred embodiment is a laminated polyester film having a layer X that satisfies the following conditions 1 and 2 on at least one side of the polyester film. Condition 1: 20 ≤ γX P ≤ 45 Condition 2: 3.0 ≤ γX H ≤ 10 γX P (mN / m): The polar component of the surface free energy of layer X γX H (mN / m): The hydrogen bond component of the surface free energy of layer X The polar component γX of the surface free energy P and the hydrogen bond component γX H are obtained by determining the static contact angles at 25 °C with glycerol, ethylene glycol, formamide, and diiodomethane with respect to the surface of layer X of the laminated polyester film, and introducing the static contact angles with each liquid and the dispersion component, polar component, and hydrogen bond component of the surface free energy of each liquid described in the following Non-Patent Document 1 into the "Hatano, Kitazaki's extended Young's equation" described in the following Non-Patent Document 2, and solving the simultaneous equations. The details of the measurement method will be described later. When layer X is not exposed, layer X is exposed by polishing until the thickness of layer X is in the range of 30 to 70% of the original thickness of layer X, and the surface free energy of layer X is determined. Non-Patent Document 1: J. Panzer: J. Colloid Interface Sci., 44, 142 (1973). Non-Patent Document 2: Yoshiaki Kitazaki, Toshio Hatano: Journal of the Adhesion Society of Japan, 8, (3) 131 (1972). The polar component γX of the surface free energy P and the hydrogen bond component γX HBy setting this range, the internal interactions of layer X itself and the interactions between layer X and the laminated polyester film are strengthened, improving solvent resistance, and layer X can be made to absorb water more easily, so that layer X can be easily removed from the laminated polyester film by washing with water or an aqueous solution. Here, solvent resistance means that, for example, even when a release layer is coated on layer X with a solvent-containing coating agent, or when a ceramic green sheet is further coated on top of that with a solvent-containing slurry, the smoothness and washability of the laminated polyester film do not deteriorate significantly. From a similar viewpoint, γX P It is more preferably 20 mN / m or more and 30 mN / m or less, and even more preferably 22 mN / m or more and 28 mN / m or less, and γX H It is more preferably 4.0 mN / m or more and 10 mN / m or less, even more preferably 6.0 mN / m or more and 10 mN / m or less, and particularly preferably 7 mN / m or more and 9 mN / m or less.

[0015] When using a resin having a polyvinyl alcohol skeleton as layer X, polar component γX P and hydrogen bonding component γX HIn order to achieve this range, one preferred embodiment is to introduce ionic polar groups such as carboxylates, sulfonates, or tertiary ammonium salts as side chain groups. Among these, sulfonates can be suitably used from the viewpoint of water solubility and solvent resistance. That is, it is more preferable that layer X contains a resin having a sulfonate-modified polyvinyl alcohol skeleton. The copolymerization amount is preferably 0.1 mol% to 10 mol%, more preferably 0.5 mol% to 10 mol%, even more preferably 0.5 mol% to 5.0 mol%, and particularly preferably 1.0 mol% to 3.0 mol% relative to the total resin having a polyvinyl alcohol skeleton. The degree of polymerization is preferably greater than 200 and less than or equal to 1000, more preferably 300 to 1000, and even more preferably 400 to 600. The degree of saponification is preferably 30 to 90, more preferably 60 to 88. Furthermore, by setting the copolymerization amount, degree of polymerization, and degree of saponification within the above ranges, the polar component γX of the surface free energy of layer X can be achieved. P and hydrogen bonding component γX H This makes it easier to define the range as described above.

[0016] In the laminated polyester film of the present invention, it is preferable that the absolute value of the difference between the contact angle HX(1) 1 second after water contacts layer X and the contact angle HX(20) 20 seconds after water contacts layer X (|HX(1)-HX(20)|) is between 5° and 60°. |HX(1)-HX(20)| represents the change in the contact angle of water before and after a certain period of time has elapsed. A small value indicates a small change in the contact angle of water before and after a certain period of time has elapsed, while a large value indicates a large change in the contact angle of water before and after a certain period of time has elapsed. Setting |HX(1)-HX(20)| to 5° or more improves the water absorption of layer X, making it easier to wash with water. Furthermore, setting |HX(1)-HX(20)| to 60° or less makes it possible to stably form layer X. Furthermore, if |HX(1)-HX(20)| is between 10° and 30°, localized uneven distribution is less likely, and rinsing performance is further improved. From the above viewpoint, it is even more preferable that it is between 10° and 25°. Also from the above viewpoint, it is even more preferable that HX(1)-HX(20)≧0°.

[0017] The layer X of the laminated polyester film of the present invention preferably contains a water-soluble substance. The inclusion of a water-soluble substance in layer X makes it easier to set |HX(1)-HX(20)| within a preferred range. Furthermore, when layer X contains a water-soluble substance, washing the laminated polyester film containing layer X with water causes layer X to dissolve in the water, making it easy to remove layer X and the layers laminated above it, thereby obtaining a high-purity polyester film. The water-soluble substance preferably constitutes 60% by mass or more of the total layer X, more preferably 90% by mass or more, even more preferably 95% by mass or more, and it is particularly preferable that it consists solely of a water-soluble substance. From the viewpoint of obtaining a high-purity polyester film, it is preferable that layer X and the polyester film are in contact.

[0018] Examples of water-soluble substances include resins with a water-soluble polyester skeleton, resins with a polyester urethane skeleton, resins with a polyvinyl alcohol skeleton (hereinafter, polyvinyl alcohol may be referred to as PVA), resins with a polyvinylpyrrolidone skeleton (hereinafter, polyvinylpyrrolidone may be referred to as PVP), and those mainly composed of starch. Here, water solubility means that the mass change when immersed in 50°C water for 10 minutes is 15% or more, and that it becomes an aqueous solution. The specific method is as follows: In other words, water solubility means that the resin is immersed in 50°C water for 10 minutes, the mass is measured after removing it from the water and thoroughly wiping off any water droplets adhering to the surface with a cloth, and the mass change ΔM calculated by the following method is 15% or more, and that it becomes an aqueous solution. ΔM = |(M2 - M1)| / M1 × 100 (%) M1(g): Mass of resin before immersion in 50°C water for 10 minutes. M2(g): Mass of resin after immersion in 50°C water for 10 minutes.

[0019] Furthermore, the term "main component" refers to a component that is present in a quantity of 60% or more by mass within 100% by mass of the layer in question.

[0020] From the viewpoint of affinity with polyester film, water solubility, and solvent resistance, layer X preferably contains a resin having a polyvinyl alcohol skeleton, and more preferably consists solely of a resin having a polyvinyl alcohol skeleton. Resins having a PVA skeleton are particularly preferred because they have few nonpolar parts and contain many hydrophilic groups, resulting in high water solubility and solvent resistance.

[0021] When using a resin having a polyvinyl alcohol skeleton as layer X, the degree of polymerization is preferably greater than 200 and 1000 or less, more preferably between 300 and 1000, and even more preferably between 400 and 600. By setting the degree of polymerization to 1000 or less, the molecular chains of polyvinyl alcohol become longer, suppressing packing within the molecular chains, allowing for a lower degree of crystallinity and increasing the elution properties of layer X. Furthermore, by setting the degree of polymerization to greater than 200, when layer X is provided by coating, the coatability can be improved, preventing uneven distribution on the film due to poor coatability and preventing deterioration of water washability due to high crystallinity. The degree of polymerization refers to the average degree of polymerization determined according to JIS K 6726 (1994).

[0022] From a similar viewpoint, if layer X contains a resin having a polyvinyl alcohol skeleton, and the average degree of polymerization of layer X is determined by the method described in JIS K 6726 (1994), it is preferable that the determined average degree of polymerization is greater than 200 and 1000 or less, more preferably 300 or more and 1000 or less, and even more preferably 400 or more and 600 or less.

[0023] Furthermore, from the above viewpoint, it is preferable that layer X contains 60% by mass or more of a resin having a polyvinyl alcohol skeleton, more preferably 90% by mass or more, even more preferably 95% by mass or more, and particularly preferable that it consists solely of a resin having a polyvinyl alcohol skeleton. In addition, it is preferable that layer X is water-soluble.

[0024] Furthermore, when a resin having a polyvinyl alcohol skeleton is used as layer X, the degree of saponification is preferably 30 to 90, more preferably 60 to 88. Polyvinyl alcohol has at least hydroxyl groups and acetate groups as side chains, but the higher the degree of saponification, the greater the amount of hydroxyl groups, which have less bulk as functional groups, and the smaller the amount of acetate groups. Therefore, when the degree of saponification is high, crystallization due to molecular chain packing tends to occur easily. Setting the degree of saponification to 90 or less allows for a lower degree of crystallinity, further improving washability. Also, setting the degree of saponification to 30 or more allows for a certain amount of acetate groups to be kept below a certain level, resulting in good washability. In addition, it becomes easier to set |HX(1)-HX(20)| within a preferred range, and solvent resistance can be improved.

[0025] Furthermore, as the resin having a polyvinyl alcohol skeleton used as layer X, copolymerized polyvinyl alcohol obtained by copolymerizing functional groups other than hydroxyl groups and acetate groups to the side chains is also a preferred embodiment. In particular, by introducing hydrophilic and bulky functional groups, such as sulfonates, γX P and γX H This makes it easier to set |HX(1)-HX(20)| within a preferred range. In particular, sulfonic acid can be suitably used from the viewpoint of water solubility and solvent resistance. That is, it is preferable that layer X contains a resin having a sulfonate-modified polyvinyl alcohol skeleton. The copolymerization amount is preferably 0.1 mol% to 10 mol%, more preferably 0.5 mol% to 5.0 mol%, and even more preferably 1.0 mol% to 3.0 mol% relative to the total amount of the resin having a polyvinyl alcohol skeleton. When the copolymerization amount is within the above range, when layer X is provided by coating, the coatability is good and it is possible to suppress uneven distribution on the film and excessive crystallinity.

[0026] As the aforementioned copolymer component, sodium sulfonate is preferred. When the copolymer component is a sodium salt as described above, the sodium can be supplied by sodium hydroxide, which is used as the alkali during saponification.

[0027] When using a resin having a polyvinyl alcohol skeleton as layer X, it is preferable that layer X does not contain acrylic resins or polyester resins that have binder properties, or crosslinking resins such as melamine or oxazoline that improve film-forming properties. Binders and crosslinking resins tend to interact with the hydroxyl groups of the side chains of the resin having a polyvinyl alcohol skeleton, making it difficult to keep |HX(1)-HX(20)| within a desirable range.

[0028] The degree of crystallinity of layer X of the laminated polyester film of the present invention is preferably 14% to 40%, more preferably 15% to 40%, and even more preferably greater than 31% and 40% or less. The degree of crystallinity generally represents the degree of crystallization of a substance; the higher the degree of crystallinity, the more crystalline portions that are free energy stable are contained in the substance. In other words, the higher the degree of crystallinity, the more stable the substance itself becomes. Setting the degree of crystallinity to 15% or more can improve solvent resistance. Setting the degree of crystallinity to 40% or less can further improve water washability. Furthermore, |HX(1)-HX(20)| can also be set as a preferred range. In addition, by setting the copolymerization amount, degree of polymerization, and degree of saponification within the above preferred ranges, the degree of crystallinity of layer X can be set within the above ranges.

[0029] The degree of crystallinity of layer X shall be determined by the method described in the examples.

[0030] A preferred embodiment of the laminated polyester film of the present invention is a laminated polyester film having a polyester film and a layer X, wherein the thickness xa (nm) of the layer X and the surface roughness RzjisB (nm) of the side of the polyester film opposite to the side with layer X (side A) (side B) satisfy the following conditions. Condition: 0.2≦RzjisB / xa≦20.0 In particular, from the viewpoint of a simpler structure and higher productivity, one more preferred embodiment is one in which the surface on the opposite side (Side B) is the surface (Side B) opposite to the surface (Side A) having layer X of the polyester film. Furthermore, from the viewpoint of improving washability, embodiments in which layer X satisfies the above-mentioned performance, or embodiments in which layer X exhibits hydrophilicity, can be cited as other more preferred embodiments. Note that layer X exhibiting hydrophilicity means that the surface free energy value measured by the method described in the examples is 10 mN / m or more. If layer X is not exposed, layer X is exposed by polishing until the thickness of layer X is in the range of 30 to 70% of the original thickness of layer X, and the surface free energy of layer X is determined.

[0031] When a film having the aforementioned layer X is stored in a humid, hot atmosphere, particularly under conditions where it is wound in a roll and subjected to surface pressure, the properties of the film may change significantly, potentially causing problems when using it. By creating a film that has the aforementioned layer X and satisfies condition 3, such changes in properties can be significantly suppressed. This will be explained in detail below.

[0032] When the laminated polyester film of the present invention is wound in a roll shape, layer X comes into contact with the surface of the polyester film on the side opposite to the side with layer X (side A) (side B). RzjisB is the 10-point average roughness measured by the method described in the examples, and a larger value indicates greater surface irregularity. If the value of RzjisB / xa is small and less than 0.2, that is, if RzjisB is small, or xa is large, or both, under conditions where surface pressure is applied in a roll shape, layer X is more likely to adhere to the surface on side B in a humid and hot atmosphere, and layer X may be transferred to the surface on side B. In addition, the shape of layer X may change, which may reduce the washability of layer X, or the coatability and function of another layer may be reduced when applying another layer in contact with layer X.

[0033] When the value of RzjisB / xa is large and exceeds 20.0, that is, when RzjisB is large, or the value of xa is small, or both, under conditions where surface pressure is applied in a roll shape, the shape of layer X may change due to the irregularities of the B-side surface itself in a humid heat atmosphere, which may reduce the washability of layer X. Also, when applying another layer in contact with layer X, the coatability and function of that layer may be reduced. From the same viewpoint as above, the value of RzjisB / xa is more preferably 1.0 to 10.0, even more preferably 1.5 to 10.0, and particularly preferably 3.0 to 8.5.

[0034] In the laminated polyester film of the present invention, it is preferable that the thickness xa (nm) of the layer X and the surface roughness RzjisX (nm) of the layer X satisfy the following condition 7. Condition 7: 0.01≦RzjisX / xa≦3.0 RzjisX refers to the surface roughness of layer X, and is the 10-point average roughness measured by the method described in the examples. In the case of a two-layer structure consisting of layer X and a polyester film, RzjisX represents the roughness of the side of layer X opposite to the side in contact with the polyester film. The roughness of layer X is affected by the roughness of side A of the polyester film, but by setting RzjisX / xa to 3.0 or less, layer X can completely cover side A, thereby improving the hydrophilicity of layer X. Furthermore, when another layer is applied in contact with layer X, the coatability and function of that layer can be fully expressed.

[0035] By setting RzjisX / xa to 0.01 or higher, the handling properties of the film can be improved. From the same viewpoint as above, RzjisX / xa is more preferably 0.5 or more and 1.5 or less.

[0036] In the laminated polyester film of the present invention, the thickness xa of layer X is preferably 10 nm or more and 500 nm or less. Setting xa to 10 nm or more makes it easier to satisfy conditions 3 and 7, thus increasing productivity. Furthermore, setting xa to 500 nm or less allows for good coatability when layer X is provided by coating.

[0037] As a preferred embodiment of the laminated polyester film of the present invention, a laminated polyester film having a layer Y satisfying the following formula on at least one surface layer can be cited. In particular, from the viewpoint of further improving washability, a laminated polyester film having a layer Y, a layer X, and a polyester film in this order can be cited as a more preferred embodiment, and a laminated polyester film having a layer Y satisfying the following conditions on the side of the layer X opposite to the side in contact with the polyester film can be cited as a particularly preferred embodiment. 80≦HY(1)≦120, 1≦|HY(1)-HY(20)|≦90 HY(1)(°): Contact angle 1 second after water comes into contact with layer Y HY(20)(°): Contact angle 20 seconds after water comes into contact with layer Y By controlling the contact angle with water and having a layer Y in which HY(1) is within the above range, the surface energy of layer Y can be reduced, making it possible to use a laminated polyester film having layer Y as a release film.

[0038] In other words, by controlling the contact angle with water and setting HY(1) to 80 ≤ HY(1), the release properties can be sufficiently high, and a laminated polyester film having layer Y can be suitably used as a release film. Furthermore, by setting HY(1) ≤ 120, when the release layer is provided by coating, the coating agent for forming the release layer is less likely to be repelled, and coating defects such as pinholes can be prevented from occurring in the release layer. From a similar viewpoint, HY(1) is more preferably 85° to 110°.

[0039] Furthermore, by changing HY(20) compared to HY(1) and setting |HY(1)-HY(20)| within the above range, it becomes possible to change the physical properties of layer Y using water as a medium. In other words, by changing the physical properties using water as a medium, the adhesion between layer Y and the laminated polyester film is changed, making it easier to remove layer Y from the laminated polyester film using water.

[0040] Setting 1 ≤ |HY(1)-HY(20)| means that layer Y is permeable to water. Setting 1 ≤ |HY(1)-HY(20)| allows more water to penetrate to the polyester film substrate, making it easier to separate layer Y from other layers at the substrate surface, thus facilitating the removal of layer Y from the laminated polyester film using water for recycling. From a similar viewpoint, setting 5 ≤ |HY(1)-HY(20)| is more preferable. Furthermore, setting |HY(1)-HY(20)| ≤ 90 stabilizes the physical properties of layer Y and suppresses deterioration of layer Y due to water vapor, etc. Furthermore, setting |HY(1)-HY(20)| ≤ 30 is more preferable because it makes it easier to form other layers on top of layer Y, and suppresses localized deterioration of water washability due to deformation or uneven distribution of layer Y when other layers are formed on top of layer Y. From a similar viewpoint as above, |HY(1)-HY(20)| is even more preferably 5° to 25°. Furthermore, from the above viewpoint, it is preferable that HY(1)-HY(20)≧0.

[0041] The methods for setting |HY(1)-HY(20)| of layer Y to the above preferred range are not particularly limited, but include methods such as ensuring that layer Y contains the resin and surfactant described later, or adding the polar component γX of the surface free energy to at least one side of the polyester film. P The hydrogen bonding component γX of the surface free energy is between 20 mN / m and 30 mN / m. H A preferred embodiment is a laminated polyester film having a layer X with a density of 6.0 mN / m or more and 10 mN / m or less, wherein the laminated polyester film has a layer Y on the side opposite to the side of the layer X that is in contact with the polyester film.

[0042] When layer X, whose surface free energy is within the aforementioned range, is in contact with layer Y, it promotes the permeation of water in contact with layer Y through layer Y, thereby increasing |HY(1)-HY(20)|. The higher the water repellency of layer Y, and the higher the water permeability of layer Y, the greater the increase in |HY(1)-HY(20)|.

[0043] As resins that can be used in layer Y of a laminated polyester film having a base material / layer Y configuration, one or more compounds selected from silicone compounds having a dimethylsiloxane skeleton, compounds having long-chain alkyl groups, compounds having a polyolefin skeleton, and fluorine-containing compounds such as perfluoroalkyl groups can be preferably listed. Among these, compounds having a polyolefin skeleton can be preferably used. Compounds with a polyolefin as the main skeleton tend to have good compatibility with surfactants described later, so it is easy to set |HY(1)-HY(20)| within the above range. Examples of compounds having a polyolefin skeleton include polymers using one of polyethylene, polypropylene, polybutadiene, hydrogenated polybutadiene, polyisoprene, hydrogenated polyisoprene, polyisobutylene, and α-olefins alone, or copolymers of two or more of these. α-olefins are olefins that have a double bond at one end of the molecular chain, such as 1-octene.

[0044] When a compound having a polyolefin skeleton is used in layer Y of a laminated polyester film consisting of a substrate / layer Y configuration, it is preferable that layer Y contains a surfactant. With this configuration, water that permeates through layer Y spreads more easily to the substrate side surface, making it easier to achieve 1 ≤ |HY(1)-HY(20)|. The amount of surfactant added per 100 parts by mass of the compound having a polyolefin skeleton is preferably 0.5 parts by mass or more and 4 parts by mass or less, and more preferably 1 part by mass or more and 2 parts by mass or less. If the amount of surfactant added is 0.5 parts by mass or more, it is a sufficient amount for the surfactant to spread throughout the entire layer Y, and water permeates through layer Y more easily. If the amount of surfactant added exceeds 4 parts by mass, the surfactant may accumulate on the surface of layer Y and contaminate the mold release material.

[0045] Examples of surfactants that can be used in layer Y of a laminated polyester film consisting of a base material / layer Y include various nonionic surfactants, such as polyoxyethylene alkyl ethers like polyoxyethylene lauryl ether, polyoxyethylene cetyl ether, polyoxyethylene stearyl ether, and polyoxyethylene oleyl ether; polyoxyethylene alkylphenyl ethers like polyoxyethylene octylphenyl ether and polyoxyethylene nonylphenyl ether; polyoxyethylene fatty acid esters like polyoxyethylene monolaurate, polyoxyethylene monostearate, and polyoxyethylene monooleate; and sorbitan monolaurate. Examples include sorbitan fatty acid esters such as sorbitan monopalmitate, sorbitan monostearate, and sorbitan monooleate; polyoxyethylene sorbitan fatty acid esters such as polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan triisostearate, polyoxyethylene sorbitan monooleate, and polyoxyethylene sorbitan trioleate; polyoxyethylene glyceryl ether fatty acid esters; and polyoxyethylene-polyoxypropylene block copolymers. These nonionic surfactants can be used individually or in combination of two or more.

[0046] Examples of highly water-repellent resins that can be used in layer Y of a laminated polyester film having a base material, layer X, and layer Y include silicone compounds having a dimethylsiloxane skeleton, compounds having long-chain alkyl groups, and compounds having fluorine. Among these, silicones having a dimethylsiloxane skeleton (organopolysiloxane) with high water permeability are preferred, and resins having a curable silicone skeleton can be suitably used. Resins having a curable silicone skeleton include "addition reaction type" resins, which are heated and cured using a platinum catalyst with an organohydrogenpolyloxane and an organopolysiloxane containing an alkenyl group; "condensation reaction type" resins, which are heated and cured using an organotin catalyst with an organohydrogenpolyloxane and an organopolysiloxane containing a hydroxyl group at the end; "UV curing type" resins, which are cured by irradiating UV light with a photopolymerization initiator, using an organopolysiloxane containing an acryloyl group or a methacryloyl group, or an organopolysiloxane containing an alkenyl group and an organopolysiloxane containing a mercapto group; and "cationic polymerization type" resins, which are cured by photo-opening the epoxy group with an onium salt initiator. Any of these can be used, but addition reaction type and UV curing type are preferred from the viewpoint of productivity and peel strength.

[0047] Specific examples of resins having an addition reaction type silicone skeleton include those containing polydimethylsiloxane and hydrogensiloxane with vinyl groups at the ends, such as KS-847, KS-847T, KS-841, KS-774, KS-3703T, and X-62-2825 from Shin-Etsu Chemical Co., Ltd., and SD7333, SRX357, SRX345, LTC310, LTC303E, LTC300B, LTC350G, LTC750A, LTC851, LTC759, LTC755, LTC761, and LTC856 from Dow Toray Industries, Inc. (Note that "LTC" is a registered trademark).

[0048] Specific examples of resins and catalysts having a condensation reaction type silicone skeleton include polydimethylsiloxane and hydrogensiloxane containing hydroxyl groups at the terminal ends, along with an organotin catalyst. Examples include SRX290 and SY LOFF23 manufactured by Dow Toray Corporation.

[0049] Specific examples of UV-curable silicone backbone resins and catalysts include those containing organopolysiloxane with acryloyl or methacryloyl groups and a photopolymerization initiator, or those containing polydimethylsiloxane with alkenyl groups and polydimethylsiloxane with mercapto groups and a photopolymerization initiator. Examples include FM-0711, FM-0721, FM-0725, FM-7711, FM-7721, FM-7725 from JNC Corporation, and BY24-510H and BY24-544 from Dow Toray Industries, Inc.

[0050] Specific examples of resins and catalysts having a cationic polymerized silicone skeleton include those containing an epoxy group-containing siloxane and an onium salt initiator, such as TPR6501, UV9300, and XS56-A2775 manufactured by Momentive Performance Materials Japan LLC.

[0051] Furthermore, it is preferable that the solvent durability rate of the surface of layer Y of the laminated polyester film of the present invention is 5% or more and 100% or less. More preferably, it is 10% or more and 100% or less. Solvent durability rate refers to the value obtained by performing a solvent-based abrasion test on the surface of layer Y of the laminated polyester film and dividing the peeling force of the surface of layer Y by the peeling force of the surface of layer Y after the abrasion test. Details of the measurement method will be described later. A higher solvent durability rate means higher solvent resistance, which can suppress deterioration of smoothness due to subsequent processes and deterioration of removeability with water. The practical upper limit of the solvent durability rate is 100%. When a resin with high removeability is used to improve reusability, the solvent durability rate tends to be lower. By keeping |HY(1)-HY(20)| within the above range and the solvent durability rate within the above range, it is possible to achieve good reusability while also having good solvent resistance.

[0052] Furthermore, the hydrogen bonding component γY of the surface free energy of layer Y of the laminated polyester film of the present invention H It is preferable that the value is between 1.5 mN / m and 10 mN / m, and more preferably between 1.5 mN / m and 5.0 mN / m. γY H By defining this range, layer Y becomes more permeable to water, which not only improves the removal of layer Y when washing with water, but also allows the water that has permeated through layer Y to peel off the layer formed on the substrate from the side closer to the substrate surface, making it easy to remove. In particular, if layer X is also present, it becomes possible to remove layer X more actively with the water that has permeated through layer Y, making it easy to remove both layer X and layer Y from the laminated polyester film.

[0053] The laminated polyester film of the present invention, taking advantage of the aforementioned properties, can be suitably used for mold release applications, where a release layer is provided on the side of layer Y opposite to the side in contact with layer X or the substrate, and the release layer is peeled off from layer Y. Furthermore, since layers X and Y can be removed from the laminated polyester film of the present invention by water, it is possible to remove layers X and Y after peeling off the molded material to obtain a high-purity polyester film. Moreover, it is preferable to remove the high-purity polyester film from the laminated polyester film of the present invention after removing layers X and Y and reuse it. It is even more preferable to remove only the polyester film after removing layers X and Y and reuse it. Methods of reuse include providing layers X and Y again to the extracted polyester film and using it as a release film, or remelting the polyester film and molding it back into a polyester film. The method of remelting and molding it back into a polyester film is not limited to reuse applications and can be used in a variety of applications, and can greatly contribute to reducing environmental impact. Therefore, it is preferable.

[0054] When a silicone compound, particularly a compound containing a dimethylsiloxane bond, is used as layer Y of the laminated polyester film of the present invention, the component containing the dimethylsiloxane bond tends to become a foreign substance when mixed with the polyester film and remelted, which can accelerate the degradation of the polyester or make it impossible to extrude it after melting. Therefore, it is preferable to remove layer Y in order to remelt and reuse the film of the present invention.

[0055] When using the laminated polyester film of the present invention having layers X and Y as a release film, the release layer can be an organic adhesive mainly composed of acrylic or an inorganic sheet mainly composed of metal or metal oxide. In particular, barium titanate, a metal oxide, is indispensable for the manufacture of MLCCs, and the amount of release film used in the process of manufacturing barium titanate sheets is increasing. Under these circumstances, by using the laminated polyester film of the present invention having layers X and Y in the process of manufacturing barium titanate sheets, layers X and Y can be removed from the laminated polyester film of the present invention after use in the process of manufacturing barium titanate sheets to obtain a high-purity polyester film for reuse, which can greatly contribute to reducing the environmental burden.

[0056] The method for producing the laminated polyester film of the present invention is described below, but the present invention is not limited to the laminated polyester film obtained by this method.

[0057] The polyester film of the laminated polyester film of the present invention can be processed into a sheet by a method (melt casting method) in which, if necessary, dried raw materials are heated and melted in an extruder and extruded from a die onto a cooled cast drum. Preferably, the sheet is cooled and solidified by electrostatic adhesion on a drum cooled to a surface temperature of 20°C to 60°C to produce an unstretched sheet. The temperature of the cast drum is more preferably 20°C to 40°C, and even more preferably 20°C to 30°C.

[0058] Next, it is preferable to biaxially stretch the unstretched sheet at a temperature T1n (°C) that satisfies equation (i) below, to a magnification of 3.6 times or more in the longitudinal direction (MD), 3.9 times or more in the width direction (TD), and 14.0 times or more and 20.0 times or less in area.

[0059] The stretching ratio in the film width direction is preferably 4.0 times or more, more preferably 4.3 times or more and 5.0 times or less. By setting the stretching ratio in the film width direction to 4.0 times or more, when layer X is applied to the uniaxially stretched film using the in-line coating method described later, the components constituting layer X are stretched and elongated in accordance with the film, which suppresses the regular arrangement of the components constituting layer X and makes it possible to keep the degree of crystallinity of layer X within a desirable range. If the stretching ratio in the width direction exceeds 5.0 times, the film-forming properties of the film may decrease. (i)Tg(℃)≦T1n(℃)≦Tg+40(℃) Tg: Glass transition temperature of polyester film (°C) A preferred method for stretching the film in the longitudinal direction is one that utilizes a speed difference between rolls. In this case, it is also preferable to stretch the film in multiple sections while fixing it with nip rolls to prevent slippage.

[0060] Next, it is preferable to obtain a polyester film by heat-setting the biaxially oriented film at a temperature (Th0 (°C)) that satisfies the following equation (ii) for 1 second to 30 seconds, then uniformly cooling it slowly and then cooling it to room temperature. (ii)Tmf-35(℃)≦Th0(℃)≦Tmf(℃) Tmf: Melting point of the film (°C) (ii) By obtaining a biaxially oriented film under conditions that satisfy (ii), the film can be given an appropriate orientation, improving its handling properties when used as a release film.

[0061] In addition to the manufacturing method described above, it is preferable to include particles in the polyester film of the laminated polyester film of the present invention in order to bring conditions 3 and 7 within the above-described ranges. The particles to be included are preferably spherical particles with a uniform particle size distribution, such as colloidal silica particles, crosslinked polystyrene particles, and calcium carbonate particles. The particle content is preferably 0.01% by mass or more and 3.0% by mass or less relative to the mass of the polyester film. Furthermore, the particle size is preferably 50 nm or more and 5000 nm or less. To satisfy condition 6, the particle size is 100 nm or more and 5000 nm or less, particularly preferably 300 nm or more and 2000 nm or less. To satisfy condition 7, the particle size is 50 nm or more and 1000 nm or less, particularly preferably 50 nm or more and 400 nm or less. In order to set conditions 6 and 7 within the preferred range for the polyester film of the present invention, it is preferable that the sheet extruded onto the cast drum has a laminated structure of two or more layers, and more preferably a laminated structure of three or more layers having an intermediate layer (C layer) between the layer constituting side A (A layer) and the layer constituting side B (B layer). In particular, when there is an intermediate layer (C layer) between layer A and layer B, it is preferable because recycled raw materials obtained by the method described later can be used for layer C.

[0062] Next, a method for providing layers X and Y in the polyester film of the laminated polyester film of the present invention will be described below, but the present invention is not limited to films obtained by this method.

[0063] When layer X is formed from a resin that easily absorbs water, a method of dissolving the resin forming layer X in water and coating it onto the polyester film of the present invention can be preferably used. As a coating method, general coating methods such as gravure coating, Meyer bar coating, air knife coating, and doctor knife coating can be used. In particular, from the viewpoint of controlling the degree of crystallinity of layer X, an in-line coating method can be preferably used, in which the resin that will form layer X is coated on the surface of the polyester film after uniaxial stretching in the longitudinal direction, and layer X is formed at the same time as the polyester film is stretched in the width direction. The thickness of layer X is preferably 10 nm or more and 500 nm or less. By setting it to 10 nm or more, the water absorption of layer X can be sufficiently expressed and the removal properties can be improved. Also, by setting it to 500 nm or less, blocking can be suppressed, which can reduce handling properties. From the same viewpoint, it is more preferably 50 nm or more and 200 nm or less.

[0064] Next, a method for providing layer Y will be described. Layer Y may be provided simultaneously with layer X or separately. When provided simultaneously, methods include applying both layers at the same time using a die or the like, or applying them using a coating agent in which the components of layer X and layer Y are pre-mixed. To improve the lamination accuracy of layer X and layer Y, it is preferable to provide layer X and layer Y separately. Layer Y can be applied to the laminated polyester film containing layer X obtained by the method described above using a coating solution in which the components of layer Y are dissolved, using common coating methods such as gravure coating, Meyer bar coating, air knife coating, or doctor knife coating. The thickness of layer Y is preferably 10 nm or more and 1000 nm or less. By setting it to 10 nm or more, the function of layer Y can be fully expressed, and by setting it to 1000 nm or less, the moisture permeability of layer Y can be fully expressed, making it easier to set |HY(1)-HY(20)| within a preferred range. From the same viewpoint, it is more preferable to be 50 nm or more and 500 nm or less.

[0065] Next, a method for removing layers X and Y will be described. Since layer X has the characteristics described above, it is preferable to wash it with water in this embodiment. For example, when removing layers X and Y, it is preferable to subject the laminated polyester film containing layers X and Y of the present invention to the following steps: unwinding the laminated polyester film, supplying hot water to the surface of the unwinded laminated polyester film to peel off the surface laminated portion (layers X and Y) from the laminated polyester film, and winding up the polyester film after peeling. The temperature of the hot water is preferably 50°C to 120°C. A temperature of 50°C or higher ensures sufficient cleaning performance. A temperature of 120°C or lower prevents the glass transition temperature of the polyester film from being exceeded, which can prevent the film from being transported. The time that water is in contact with the surface of the laminated polyester film is preferably 5 seconds or more, more preferably 10 seconds or more, and even more preferably 30 seconds to 600 seconds. The step of supplying hot water to the surface of the unwinded laminated polyester film can be performed in a water tank, covering the entire laminated polyester film, or by pressurizing heated water and spraying it onto the laminated polyester film. By supplying water to layer Y of the laminated polyester film, water is absorbed through layer Y to layer X and the substrate, changing the physical properties of layer Y. As a result, layer Y becomes easier to peel from the laminated polyester film, improving washability. In the above process, the conveying speed of the laminated polyester film is 5 m / min or more, preferably 10 m / min or more, and more preferably 20 m / min or more and 100 m / min or less. In the process of removing layers X and Y, when conveying the laminated polyester film with layers X and Y, applying tension to the laminated polyester film is also a preferred embodiment. By applying tension, the surface of the laminated polyester film is stretched, improving the peelability of layers X and Y, and thus improving washability. The tension is preferably 5 N / m or more and 100 N / m or less, more preferably 20 N / m or more and 80 N / m or less, and even more preferably 30 N / m or more and 50 N / m or less. By setting the tension to 5 N / m or more as described above, the surface of the laminated polyester film is sufficiently stretched, and good washability can be achieved.Furthermore, by keeping the tension below 100 N / m, it is possible to suppress wrinkles in the film and reduce the surface stretchability, thereby improving washability.

[0066] Next, a preferred embodiment of a method for using a film from which layers X and Y have been removed as recycled raw material will be described. It is preferable to introduce the film roll from which layers X and Y have been removed by the method described above into a crusher having a motor-driven rotating blade to crush it, then introduce it into an extruder to melt it, extrude it into strands, and cut it into pellets to obtain recycled raw material. The melting temperature is preferably 250°C to 300°C in order to keep the intrinsic viscosity of the recycled raw material within a desirable range. The extruder may have a single or twin screw. The film from which layers X and Y have been removed may contain particles in the film itself or residue from when layers X and Y were removed, so it is preferable for the extruder to have twin screw from the viewpoint of uniformly mixing the contained components. It is also preferable to filter the film during melt extrusion in order to keep components other than polyester within an appropriate range. The obtained recycled raw material can be used as raw material for the above-mentioned layers A, B, and C.

[0067] The obtained recycled raw material preferably contains components other than polyester in an amount of 0.0001% by mass or more and 0.3% by mass or less. If the amount of components other than polyester exceeds 0.3% by mass, depending on the manufacturing equipment, a large amount of foreign matter may be generated when a film is made using the recycled raw material, making it difficult to obtain the desired properties. For example, when the recycled raw material is used for layer A or layer B of the laminated film of the present invention, the surface properties of layer A or layer B may not be satisfied. If the amount of impurities is reduced to less than 0.0001% by mass of polyester, the damage to the base film during the process of removing layers X and Y becomes large, and it may become difficult to obtain recycled polyester.

[0068] The recycled material may be used in layer A, layer B, or layer C, but its use in layer C is particularly preferred. Since the recycled material may contain particles other than polyester that are present in the laminated film, using the recycled material in layer A or B may affect the surface properties of those layers. On the other hand, using the recycled material in layer C, which is an intermediate layer between layers A and B, is preferable because layer C has no surface, and therefore its surface properties are not impaired even when recycled material is used.

[0069] A preferred embodiment of the laminated polyester film of the present invention is as described above, in which, after providing layer X on at least one side of the polyester film, layer Y is provided and used as a release film for the process or other functional performance layer film, and then layers X and Y are washed off with water to obtain a high-purity polyester film. As a result, the obtained polyester film can be reused as is, or the film can be remelted and chipped and used as a recycled raw material in film making and reused as a film. As a recycled raw material, from the viewpoint of film-forming properties, the intrinsic viscosity (IV) is 0.5 or more and 0.7 or less, and particularly preferably 0.55 or more and 0.65 or less.

[0070] [Method for evaluating characteristics] A. Thickness of each layer The thickness of each layer of the laminated film is determined by the following method: A cross-section of the film is cut using a microtome in a direction parallel to the film width. The cross-section is observed with a scanning electron microscope at a magnification of 5000x, and the thickness of each laminated layer is measured.

[0071] B. Intrinsic viscosity (IV) The polyester film of the present invention is dissolved in 100 ml of orthochlorophenol (solution concentration C = 1.2 g / dl), and the viscosity of the solution at 25°C is measured using an Ostwald viscometer. The viscosity of the solvent is also measured in the same manner. Using the obtained solution viscosity and solvent viscosity, [η] (dl / g) is calculated using the following formula (a), and the obtained value is taken as the intrinsic viscosity (IV). (a)ηsp / C=[η]+K[η] 2 ·C (Here, ηsp = (solution viscosity (dl / g) / solvent viscosity (dl / g)) - 1, and K is the Huggins constant (assumed to be 0.343).)

[0072] B-2. Amount of terminal carboxyl groups The amount of terminal carboxyl groups (COOH terminal groups) is determined by the method described in International Publication No. 2010 / 103945.

[0073] C. Compositional analysis of layer X The time-of-flight secondary ion mass spectrometry (TOF-SIMS) spectrum and Fourier transform infrared spectroscopy (FT-IR) spectrum of layer X will be measured to analyze the presence or absence of polyvinyl alcohol skeletons and other components. [TOF-SIMS measurement conditions] The TOF-SIMS spectrum is measured on the surface of layer X using the following apparatus. Equipment: TOF.SIMS5 manufactured by ION-TOF Corporation Primary ion species: Bi3 ++ Primary ion acceleration voltage: 25kV Pulse width: 125ns Punching: None (High spatial resolution measurement) Raster size: 40μm x 40μm Number of scans: 64 Polarity of secondary ions: positive Neutralization of static charge: Yes Subsequent acceleration voltage: 9.5kV. [FT-IR measurement conditions] The FT-IR spectrum is measured on the surface of layer X using the following apparatus. Equipment: PerkinElmer Spectrum100 Light source: Special ceramics Detector: DTGS Resolution: 4cm -1 Total number of times: 256 Measurement wavefrequency range: 4,000~680cm -1 Measurement mode: Attenuated Total Reflectance (ATR) method Included device: Single-reflection ATR crystal (Material: Diamond / ZnSe).

[0074] C-2. Copolymerization amount of layer X (mol%) Using the following equipment, 13 The copolymerization amount (mol%) is determined from the peak area of ​​the carbon signal at the introduction of the modifying group in the 1C NMR spectrum and DEPT135 spectrum. Equipment: ECZ-600R (manufactured by JEOL RESONANCE Co., Ltd.) Measurement method: Single 13 C pulse with inverse gated1H decoupling Measurement frequency: 150.9MHz Pulse width: 5.25 μs Lock solvent: D2O Chemical shift standard: TSP (0 ppm) Total count: 10,000 times Measurement temperature: 20℃ Sample rotation speed: 15 Hz.

[0075] D. Degree of saponification of layer X In accordance with JIS K 6726 (1994) Polyvinyl Alcohol Test Method, the amount of acetate groups contained in the sample is quantified and calculated by titration with an aqueous sodium hydroxide solution.

[0076] E. Average degree of polymerization of layer X In accordance with the JIS K 6726 (1994) polyvinyl alcohol test method, the sample is completely saponified with an aqueous sodium hydroxide solution, and then the viscosity at 25°C is measured using the Ostwald viscosity system. The average degree of polymerization is calculated from the intrinsic viscosity.

[0077] F. Surface free energy of layer X The following method is used to measure the contact angle using a DM501 contact angle meter manufactured by Kyowa Interface Science Co., Ltd. and its accompanying analysis software FAMAS. Glycerol, ethylene glycol, formamide, and diiodomethane are used as standard solutions on the surface of layer X, and the static contact angle of each liquid at 25°C is determined. The static contact angle of each liquid, along with the dispersion component, polar component, and hydrogen bonding component of the surface free energy of each liquid as described in Non-Patent Literature 1, are introduced into the "Hata and Kitazaki Extended Hawks Equation" described in Non-Patent Literature 2, and the dispersion component, polar component, and hydrogen bonding component of the surface free energy of layer X are determined by solving the simultaneous equations.

[0078] The static contact angle is measured by first letting the sample stand at 25°C for 12 hours. The time the droplet is in contact with the sample surface is set to 0 seconds, and the static contact angle is calculated using the image taken 30 seconds later and the θ / 2 method. Five measurements are taken at different locations, and the average value of the static contact angle is used to calculate the dispersion component, polar component, and hydrogen bonding component of the surface free energy of layer X.

[0079] G. Surface free energy of layer Y Except for using benzyl alcohol, ethylene glycol, formamide, and diiodomethane as standard solutions, the measurement is performed in the same manner as the surface free energy of layer X.

[0080] H. Water contact angle (°) The following method is used to measure the contact angle using the DM501 contact angle meter and accompanying analysis software FAMAS manufactured by Kyowa Interface Science Co., Ltd. Under an atmosphere of 23°C and 65% RH, a video of the water droplet shape is recorded for 20 seconds, with the time of contact with the sample surface set to 0 seconds. Five measurements are taken at different locations. When the sample surface in contact with the water droplet is layer X, the average contact angle obtained from the water droplet shape at 1 second and 20 seconds is calculated and designated as HX(1) and HX(20), respectively. When the sample surface in contact with the water droplet is layer Y, the same calculation is performed and designated as HY(1) and HY(20).

[0081] H-2. Crystallinity of layer X Using the following apparatus and conditions, the spectrum of the laminated polyester film on the X-side surface was measured by the FT-IR ATR method. Then, the spectrum of Toray Industries, Inc.'s polyester film "Lumirror" (registered trademark) #50T60, which was measured similarly, was divided to obtain the difference spectrum. Next, at wavenumber 1400 cm⁻¹... -1 ~1550cm -1 When the minimum absorbance between these values ​​is used as the baseline, wavenumber 1400 cm⁻¹ -1 ~1450cm -1 Let c be the value of the maximum absorbance between these points, and wavenumber 1100 cm. -1 ~1200cm -1 When the line connecting the two minimum absorbance values ​​between these points is used as the baseline, at wavenumber 1130 cm⁻¹ -1 ~1150cm -1 Let d be the value of the maximum absorbance between these two values, and calculate the crystallinity of layer X based on the formula "Percent crystallinity = 92(d / c)-18" described in Non-Patent Literature (J. Polymer Science: Part A-1, Vol. 4, p679-698 (1966)). Note that in calculating c and d above, if there are two or more maximum absorbance values ​​within the relevant wavenumber range, use the larger absorbance value to calculate c and d. Also, for wavenumber 1100 cm⁻¹... -1 ~1200cm -1 If there are three or more minimum absorbance values ​​between the two points, the baseline is determined using the two points with the lowest absorbance. Also, the surface of the laminated polyester film on the layer X side may be either layer X as the outermost surface or layer Y as the outermost surface. Equipment: 670-IR (Varian FT-IR) Light source: Grover Detector: DLatgs (Deuterated L-alanine-doped triglycine sulfate) Resolution: 4cm -1 Total number of times: 256 Measurement method: Attenuated total reflection method Attached device: Single-reflection ATR measurement attachment device (The Seagull TM ) ATR crystal; germanium Incident angle: 60° Polarization: None.

[0082] I. Solvent durability (%) The measurement will be performed using a JSPS-type testing machine (compliant with JIS L 0849 (2013)) manufactured by Daiei Kagaku Seiki Seisakusho Co., Ltd., according to the following method. [Abrasion treatment using solvent-impregnated cloth] The surface of layer Y of the film is subjected to abrasion treatment using the following testing machine and abrasive. Testing machine: Japan Society for the Promotion of Science type testing machine (Type II friction testing machine as described in JIS L 0849 (2013)) Friction element: Cotton cloth (metal cloth No. 3) impregnated with a toluene:ethanol mixed solvent (mass ratio 1:1) Load: 1.0kg Number of round trips: 30 [Peeling treatment] A polyester adhesive tape (Nitto Denko Corporation No. 31B, 19 mm wide) is applied to the abraded portion of the surface of layer Y using a 2.0 kg roller under pressure. After standing for 24 hours in an atmosphere of 23°C and 65% RH, the peel force between the sample surface and the polyester adhesive tape is measured using a peel tester VPA-H200 manufactured by Kyowa Interface Science Co., Ltd. at a peel angle of 180° and a peel speed of 300 mm / min. F(B) is calculated by converting this to a 50 mm width. The peel force F(A) of the layer Y surface before abrasion is also measured using the same method, and the solvent durability rate is measured based on the following formula. Solvent durability rate (%) = F(A) / F(B) × 100 J. Peelability of the mold to be released Polyester adhesive tape (Nitto Denko Corporation No. 31B, 19mm wide) is applied to the surface of the release material of a laminated polyester, which consists of multiple layers of release material. The strength is measured using a peel tester VPA-H200 manufactured by Kyowa Interface Science Co., Ltd. at a peel angle of 180° and a peel speed of 300mm / min, and the result is converted to a 50mm width.

[0083] Solvent resistance as an indicator of K. haze change After peeling the release material from the laminated polyester, the haze Hz(B) is measured using a NDH-5000 haze meter manufactured by Nippon Denshoku Co., Ltd., in accordance with JIS K 7136 (2000). The haze Hz(A) of the laminated polyester before the release material is laminated is also measured using the same method, and ΔHz is calculated based on the following formula. ΔHz = Hz(B) - Hz(A) L. Solvent resistance as an indicator of surface roughness change The surface roughness Sa(A) of the laminated polyester before lamination of the release material and the surface roughness Sa(B) after peeling the release material off the laminated polyester were measured using the non-contact surface shape measurement system "VertScan" (registered trademark) R550H-M100 manufactured by Ryoka Systems Co., Ltd. under the following conditions, and ΔSa was calculated based on the following formula. The arithmetic mean of five measurements was adopted for the surface roughness. ΔSa = Sa(B) - Sa(A) (Measurement conditions) • Measurement mode: WAVE mode. Objective lens: 50x. • 0.5x Tube lens. ·Measurement area: 187 x 139μm.

[0084] Evaluation of the removeability of layers X and Y. Using the polyester film obtained by removing layers X and Y, measure the water contact angle obtained after 1 second according to item H above, and make the following determination.

[0085] A; 65° or more and less than 80° B; 80° or more but less than 90°, or less than 65° C; 90° or more and less than 95°.

[0086] D; 95° or more and less than 98°.

[0087] E; 98° or higher.

[0088] N. Reusability After removing layers X and Y, the polyester film is crushed, dried at 180°C for 2 hours, then put into an extruder and melt-extruded at 280°C. It is then formed into a sheet on a cast drum cooled to 25°C, and the intrinsic viscosity of the resulting sheet is measured by method B. above. A smaller difference (ΔIV) between the intrinsic viscosity IV(R) of the sheet and the intrinsic viscosity IV of the polyester film is desirable.

[0089] O.RzjisB, RzjisX (nm) The three-dimensional surface roughness of the sample was measured using the following equipment and conditions. The ten-point average surface roughness Rzjis was calculated using analysis software. The measurement was repeated 10 times at different locations, and the average values ​​were used as RzjisB and RzjisX (nm). Equipment: Surf-Corder ET-4000A manufactured by Kosaka Laboratory Analysis software: i-Face model TDA31 Stylus tip radius: 0.2μm Measurement field of view: X direction: 380 μm, Pitch: 1 μm Y-direction: 280 μm, Pitch: 5 μm Tracking force: 50μN Measurement speed: 0.1mm / s Cutoff values: Low frequencies; 0.8mm, High frequencies; None Leveling: Entire area Filter: Gaussian filter (2D) Magnification: 100,000 times.

[0090] P. Amount of components other than polyester in recycled raw materials (mass %) A predetermined amount of the sample is dissolved in orthochlorophenol at 160°C for 40 minutes and filtered through a glass filter (3G3). After filtration, the residue is washed with dichloromethane and hot-air dried at 130°C for 10 hours. The residue is then weighed, and the percentage of the residue mass relative to the sample before dissolution is calculated (mass%).

[0091] Q. Removability of layers X and Y after moist heat treatment The remaining laminated polyester film with layer X, obtained by the method of each embodiment, is wrapped in a moisture-proof packaging material (aluminum tube manufactured by Nagaoka Sangyo Co., Ltd.) while still in roll shape and left to stand for 7 days in an atmosphere of 60°C and 80% relative humidity. After that, the laminated polyester film with layer X is removed, and layer Y is applied to the side of layer X opposite to the side in contact with the polyester film using the gravure coating method with coating agent A described later to a thickness of 0.1 μm, thereby obtaining a laminated polyester film with layer X and layer Y laminated together. Furthermore, the laminated polyester film with layer X and layer Y thus prepared is used as a release film, and the dielectric paste described later is applied to the side of layer Y opposite to the side in contact with layer X as the material to be released, using the die coating method to a thickness of 1.0 μm after drying. After that, a release film roll for the process is obtained from the obtained laminate, from which the dielectric has been released and the material to be released has been peeled off. The film roll is introduced into a water washing device equipped with an unwinding and winding mechanism, and washed with 60°C water for 2 minutes under a tension of 100 N / m to remove layers X and Y. The polyester film after the removal of layers X and Y is evaluated for the ease of removing layers X and Y as described in M. [Examples]

[0092] The present invention will be described below with reference to examples, but the present invention is not necessarily limited to these examples.

[0093] [Preparation of PET-1] Molten polymerized PET was obtained by conventional polymerization using terephthalic acid and ethylene glycol as catalysts, with antimony trioxide and magnesium acetate tetrahydrate. The obtained molten polymerized PET had a glass transition temperature of 81°C, a melting point of 255°C, an intrinsic viscosity of 0.65, and a terminal carboxyl group content of 20 eq. / t.

[0094] [Preparation of MB-A] 80 parts by mass of PET-1 and 10 parts by mass of a 10% by mass aqueous slurry of 0.1 μm cross-linked polystyrene particles (styrene-acrylate copolymer) (1 part by mass as cross-linked polystyrene particles) were supplied. The vent holes were kept under reduced pressure of 1 kPa or less to remove water, and MB containing 1% by mass of cross-linked polystyrene particles was obtained. The glass transition temperature was 81°C, the melting point was 255°C, the intrinsic viscosity was 0.61, and the amount of terminal carboxyl groups was 22 eq. / t.

[0095] [Preparation of MB-B] 80 parts by mass of PET-1 and calcium carbonate particles with a particle size of 1.0 μm were supplied, and the vent hole was maintained at a reduced pressure of 1 kPa or less to remove moisture, thereby obtaining MB containing 1% by mass of the particles. The glass transition temperature was 81°C, the melting point was 255°C, the intrinsic viscosity was 0.61, and the amount of terminal carboxyl groups was 22 eq. / t.

[0096] [Preparation of MB-C] Using PET-1 and alumina silicate particles with a particle size of 4.0 μm, MB-C was obtained by kneading while removing moisture under reduced pressure of 1 kPa or less with the vent holes maintained at a reduced pressure of 1 kPa or less, so that the alumina silicate particles contained 1.0 mass% of the total MB-C. The glass transition temperature was 81°C, the melting point was 255°C, the intrinsic viscosity was 0.61, and the amount of terminal carboxyl groups was 22 eq. / t.

[0097] [Preparation of MB-D] Using a 10% by mass aqueous slurry of PET-1 and 0.2 μm cross-linked polystyrene particles (styrene-acrylate copolymer), the mixture was fed into a vented extruder so that the cross-linked polystyrene particles constituted 2% by mass of the total MB-D. The mixture was kneaded while maintaining a reduced pressure of 1 kPa or less to remove moisture, thereby obtaining MB-D. The glass transition temperature was 81°C, the melting point was 255°C, the intrinsic viscosity was 0.61, and the amount of terminal carboxyl groups was 22 eq. / t. [Preparation of PEN] A transesterification reaction was carried out from dimethyl 2,6-naphthalenedicarboxylate and ethylene glycol using manganese acetate as a catalyst. After the transesterification reaction was completed, PEN was obtained by a conventional method using antimony trioxide as a catalyst. In addition, 0.1 μm δ-crystalline alumina particles were added during polymerization so that the content was 0.1%. The obtained PEN had a glass transition temperature of 124°C, a melting point of 265°C, an intrinsic viscosity of 0.62, and a terminal carboxyl group content of 25 eq. / t.

[0098] [Preparation of coating agent A] 100 parts by mass of an addition-reaction type silicone resin release agent (product name KS-847T, manufactured by Shin-Etsu Chemical Co., Ltd.) and 1 part by mass of a platinum catalyst (product name CAT-PL-50T, manufactured by Shin-Etsu Chemical Co., Ltd.) were mixed with toluene as a solvent to obtain coating agent A, which has a solid content of 1.5% by mass.

[0099] [Preparation of coating agent B] 100 parts by mass of a condensation reaction type silicone resin release agent (product name SRX290, manufactured by Dow Toray Corporation) and 6 parts by mass of a curing agent (product name SRX242C, manufactured by Dow Toray Corporation) were prepared with toluene as the solvent to obtain coating agent B with a solid content of 1.5% by mass.

[0100] [Preparation of coating agent C] Two parts by mass of UV-curable silicone resin release agent (product name FM-7721, manufactured by JNC Corporation), 100 parts by mass of 1,9-nonanediol diacrylate (product name "Viscote" (registered trademark) #260, manufactured by Osaka Organic Chemical Industry Co., Ltd.), and two parts by mass of photopolymerization initiator (product name "OMNIRAD" (registered trademark) 184, manufactured by IGM RESINS) were mixed with toluene as the solvent to obtain coating agent C, which has a solid content of 1.5% by mass.

[0101] [Preparation of coating agent D] Referring to Patent Document No. 9-227627, PVA was prepared with a degree of saponification of 88, an average degree of polymerization of 500, and a copolymer amount of sodium sulfonate of 0.1 mol%. This PVA was dissolved in water to a concentration of 4% by mass to obtain coating agent D.

[0102] [Preparation of coating agent E] Referring to Patent Publication No. 9-227627, PVA was prepared with a degree of saponification of 88, an average degree of polymerization of 500, and a copolymer amount of sodium sulfonate of 0.5 mol%. This PVA was dissolved in water to a concentration of 4% by mass to obtain coating agent E.

[0103] [Preparation of coating agent F] Referring to Patent Publication No. 9-227627, PVA was prepared with a degree of saponification of 88, an average degree of polymerization of 500, and a copolymer amount of sodium sulfonate of 1 mol%. This PVA was dissolved in water to a concentration of 4% by mass to obtain coating agent F.

[0104] [Preparation of coating agent G] Referring to Patent Publication No. 9-227627, PVA was prepared with a degree of saponification of 88, an average degree of polymerization of 400, and a copolymer amount of sodium sulfonate of 3 mol%. This PVA was dissolved in water to a concentration of 4% by mass to obtain coating agent G.

[0105] [Preparation of coating agent H] Referring to Patent Document No. 9-227627, PVA was prepared with a degree of saponification of 88, an average degree of polymerization of 300, and a copolymer amount of sodium sulfonate of 5 mol%. This PVA was dissolved in water to a concentration of 4% by mass to obtain coating agent H.

[0106] [Preparation of coating agent I] Referring to Patent Publication No. 9-227627, PVA was prepared with a degree of saponification of 88, an average degree of polymerization of 1000, and a copolymer amount of sodium sulfonate of 1 mol%. This PVA was dissolved in water to a concentration of 4% by mass to obtain coating agent I.

[0107] [Preparation of coating agent J] Referring to Patent Document No. 9-227627, PVA was prepared with a degree of saponification of 88, an average degree of polymerization of 300, and a copolymer amount of sodium sulfonate of 1 mol%. This PVA was dissolved in water to a concentration of 4% by mass to obtain coating agent J.

[0108] [Preparation of coating agent K] Polyvinyl alcohol "GL-05" (saponification degree 88, average degree of polymerization 500) manufactured by Mitsubishi Chemical Corporation was dissolved in water to a concentration of 4% by mass to obtain coating agent K.

[0109] [Preparation of coating agent L] Referring to Patent Document JP 2008-291120, PVA was prepared with a degree of saponification of 88, an average degree of polymerization of 1000, and a copolymer amount of sodium carboxylate of 1 mol%. This PVA was dissolved in water to a concentration of 4% by mass to obtain coating agent L.

[0110] [Preparation of coating agent M] Referring to Patent Document No. 2004-285143, PVA was prepared with a degree of saponification of 88, an average degree of polymerization of 450, and a copolymer amount of 1,2-ethanediol of 6 mol%. This PVA was dissolved in water to a concentration of 4% by mass to obtain coating agent M.

[0111] [Preparation of coating agent N] Referring to Patent Publication No. 9-227627, PVA was prepared with a degree of saponification of 98, an average degree of polymerization of 500, and a copolymer amount of sodium sulfonate of 1 mol%. This PVA was dissolved in water to a concentration of 4% by mass to obtain coating agent N.

[0112] [Preparation of coating agent O] Referring to Patent Publication No. 9-227627, PVA was prepared with a degree of saponification of 88, an average degree of polymerization of 2500, and a copolymer amount of sodium sulfonate of 1 mol%. This PVA was dissolved in water to a concentration of 4% by mass to obtain coating agent O.

[0113] [Preparation of dielectric paste] 100 parts by mass of barium titanate (product name HPBT-1, manufactured by Fuji Titanium Industries Co., Ltd.), 10 parts by mass of polyvinyl butyral (product name BL-1, manufactured by Sekisui Chemical Co., Ltd.), 5 parts by mass of dibutyl phthalate, and 60 parts by mass of toluene-ethanol (mass ratio 30:30) were mixed with glass beads having a number average particle size of 2 mm. The mixture was then mixed and dispersed in a jet mill for 20 hours, and then filtered to produce a dielectric paste.

[0114] [Preparation of Adhesive Q] 97 parts by mass of butyl acrylate, 3 parts by mass of acrylic acid, 0.2 parts by mass of azobisisobutyronitrile and 233 parts by mass of ethyl acetate were added as polymerization initiators. Nitrogen gas was then flowed through the mixture, and nitrogen purging was performed for approximately 1 hour while stirring. Subsequently, the flask was heated to 60°C and reacted for 7 hours to obtain an acrylic polymer with a weight-average molecular weight (Mw) of 1.1 million. To this acrylic polymer solution (solid content of 100 parts by mass), 0.8 parts by mass of trimethylolpropanetylene diisocyanate (trade name "Coronate" (registered trademark) L, manufactured by Nippon Polyurethane Industry Co., Ltd.) and 0.1 parts by mass of a silane coupling agent (trade name "KBM-403," manufactured by Shin-Etsu Chemical Co., Ltd.) were added to prepare an adhesive composition (adhesive Q).

[0115] [Preparation of coating agent R] Referring to Patent Publication No. 9-227627, PVA was prepared with a degree of saponification of 88, an average degree of polymerization of 300, and a copolymer amount of 1,2-ethanediol of 10 mol%. This PVA was dissolved in water to a concentration of 4% by mass to obtain coating agent R.

[0116] [Preparation of coating agent S] Referring to Patent Publication No. 9-227627, PVA was prepared with a degree of saponification of 88, an average degree of polymerization of 200, and a copolymer amount of sodium sulfonate of 3 mol%. This PVA was dissolved in water to a concentration of 4% by mass to obtain coating agent S.

[0117] [Preparation of coating agent T] Referring to Patent Document No. 2004-230772, ethylene propylene copolymer and ethylene hexene copolymer were synthesized separately. 53 parts by mass of ethylene propylene copolymer, 42 parts by mass of ethylene hexene copolymer, and 1 part by mass of Kao Corporation's nonionic surfactant (polyoxyethylene sorbitan monolaurate) "Leodol" (registered trademark) TW-L120 were mixed with toluene-ethyl acetate (mass ratio 85:15) as a solvent to obtain coating agent T, which has a solid content of 1.5% by mass.

[0118] (Example 1) As raw materials for layers A and B, 80 parts by mass of PET-1 and 20 parts by mass of MB-A were mixed, vacuum dried at 160°C for 2 hours, then fed into an extruder, melted at 280°C, and extruded through a die onto a casting drum with a surface temperature of 25°C to produce an unstretched sheet. Subsequently, the sheet was preheated with a group of heated rolls, then stretched 3.8 times in the longitudinal direction (MD direction) at 90°C, and then cooled with a group of rolls at 25°C to obtain a uniaxially oriented film. Coating agent D was applied to the obtained uniaxially oriented film by bar coating so that the coating thickness after drying would be 100 nm. Subsequently, while holding both ends of the film with clips, it was stretched 4.3 times in the width direction (TD direction) perpendicular to the longitudinal direction in a heating zone at 100°C inside a tenter. Furthermore, it was heat-set for 10 seconds at 230°C in a heat treatment zone inside the tenter. Next, after uniform slow cooling in a cooling zone, the material was wound up to obtain a laminated polyester film in which layer X was laminated.

[0119] A layer Y was obtained by applying coating agent A to the side of layer X of the obtained laminated polyester film that is opposite to the side in contact with the polyester film, using a gravure coating method, so that the thickness after drying is 100 nm.

[0120] A dielectric paste was applied to the obtained laminated polyester film by die coating to a thickness of 1.0 μm after drying, and 15 seconds after application, it was dried for 2 minutes in an oven at 100°C with an airflow of 5 m / s. Subsequently, the dielectric (release material) was released from the resulting laminate, and a film roll was obtained by winding up the laminated polyester film from which the release material had been removed. The film roll was introduced into a water washing device equipped with an unwinding and winding device, and washed with 100°C water for 2 minutes under a tension of 30 N / m to remove layers X and Y, and the polyester film was recovered.

[0121] The evaluation results are shown in the table.

[0122] (Examples 2-7) A laminated polyester film was prepared in the same manner as in Example 1, except that coating agent E was used as layer X in Example 2, coating agent F in Example 3, coating agent G in Example 4, coating agent H in Example 5, coating agent I in Example 6, and coating agent J in Example 7. After laminating the release material, it was peeled off, and then layers X and Y were removed, and the polyester film was reused.

[0123] (Examples 8 and 9) A laminated polyester film was prepared in the same manner as in Example 3, except that the thickness of layer X was changed as shown in the table. After laminating the release material, it was peeled off, and then layers X and Y were removed, and the polyester film was reused.

[0124] (Example 10) A laminated polyester film was prepared in the same manner as in Example 3, except that the polyester raw material used was changed to PEN. After laminating the release material, it was peeled off, and then layers X and Y were removed to reuse the polyester film.

[0125] (Examples 11 and 12) A laminated polyester film was prepared in the same manner as in Example 3, except that the thickness of layer Y was changed as shown in the table. After laminating the release material, it was peeled off, and then layers X and Y were removed and the polyester film was reused. In addition, in Q. Evaluation of the removeability of layers X and Y after moist heat treatment, the thickness of layer Y was changed as shown in the table for evaluation.

[0126] (Example 13) A laminated polyester film was prepared in the same manner as in Example 3, except that coating agent B was used for layer Y. After laminating the release material, it was peeled off, and then layers X and Y were removed and the polyester film was reused. Q. In evaluating the removeability of layers X and Y after moist heat treatment, coating agent B was used instead of coating agent A for layer Y.

[0127] (Example 14) For layer Y, coating agent C was used, and after drying, the integrated light intensity was 200 mJ / cm² under an atmosphere of 0.1% oxygen concentration. 2 Except for UV irradiation, a laminated polyester film was prepared in the same manner as in Example 3. After laminating the release material, it was peeled off, and then layers X and Y were removed and the polyester film was reused. Q. In evaluating the removeability of layers X and Y after moist heat treatment, coating agent C was used as layer Y instead of coating agent A, and after drying, the integrated light intensity was 200 mJ / cm² in an atmosphere with an oxygen concentration of 0.1 volume%. 2 The layers Y were stacked and evaluated after UV irradiation.

[0128] (Examples 15-17) Laminated polyester films were prepared in the same manner as in Example 1, except that coating agent K was used as layer X in Example 15, coating agent L in Example 16, and coating agent M in Example 17. After laminating the release material, the layers were peeled off, and then layers X and Y were removed to reuse the polyester film.

[0129] (Example 19) As raw materials for sides A and B, 30 parts by mass of PET-1 and 20 parts by mass of MB-B were mixed, vacuum dried at 160°C for 2 hours, then fed into an extruder, melted at 280°C, and extruded through a die onto a casting drum with a surface temperature of 25°C to produce an unstretched sheet. Subsequently, the sheet was preheated with a group of heated rolls, then stretched 3.8 times in the longitudinal direction (MD direction) at 90°C, and then cooled with a group of rolls at 25°C to obtain a uniaxially oriented film. Coating agent F was applied to side A of the obtained uniaxially oriented film by bar coating so that the coating thickness after drying and stretching was 100 nm. Subsequently, while holding both ends of the film with clips, it was stretched 4.3 times in the width direction (TD direction) perpendicular to the longitudinal direction in a heating zone at 100°C inside a tenter. Furthermore, it was heat-set for 10 seconds at 230°C in a heat treatment zone inside the tenter. Next, after uniform slow cooling in a cooling zone, the material was wound into a roll shape to obtain a laminated polyester film with layer X laminated on top of it. Using a portion of the obtained laminated polyester film with layer X laminated on top of it, coating agent A was applied to the upper surface of layer X (the surface opposite to the surface where layer X is in contact with the polyester film) as layer Y with a thickness of 0.1 μm using the gravure coating method to obtain a laminated polyester film with layer X and layer Y laminated on top of it. Furthermore, the laminated polyester film with layer X and layer Y thus prepared was used as a release film, and a dielectric paste was applied to the surface of layer Y opposite to the surface in contact with layer X as the material to be released, using the die coating method to obtain a thickness of 1.0 μm after drying. Subsequently, a release film roll for the process of releasing the dielectric and peeling off the material to be released was obtained from the obtained laminate. The film roll was introduced into a water washing device equipped with an unwinding and winding device, and washed with 60°C water for 2 minutes under a tension of 100 N / m to remove layer X and layer Y.

[0130] (Example 20) A laminated polyester film was obtained by laminating layer X in the same manner as in Example 19, except that the thickness of layer X was as shown in the table, a polyester film in which layer X and layer Y were laminated, and a release film were obtained. The characteristics of each are shown in the table.

[0131] The release properties of layers X and Y in the laminated film having layer X when not stored in a humid, hot atmosphere, and in the release film having layer X after being stored in a humid, hot atmosphere, were at a level that posed no practical problems, and the film was suitable for use as a release film.

[0132] (Example 21) As the raw material for side A, 95 parts by mass of PET-1 and 5 parts by mass of MB-D were mixed and vacuum-dried at 160°C for 2 hours. As the raw material for side B, 50 parts by mass of PET-1 and 50 parts by mass of MB-B were mixed and vacuum-dried at 160°C for 2 hours. These raw materials were fed into separate extruders, melted at 280°C, and laminated through a consolidation device so that the thickness of the layer constituting side A (layer A) and the thickness of the layer constituting side B (layer B) were 5 / 95. The sheets were then extruded through a die onto a casting drum with a surface temperature of 25°C to produce an unstretched sheet. Subsequently, the sheet was preheated with a group of heated rolls, stretched 3.8 times in the longitudinal direction (MD direction) at a temperature of 90°C, and then cooled with a group of rolls at a temperature of 25°C to obtain a uniaxially oriented film. On the A-side of the obtained uniaxially oriented film, coating agent F was applied by bar coating so that the coating thickness after drying and stretching was 100 nm. Subsequently, while holding both ends of the film with clips, it was stretched 4.3 times in the width direction (TD direction) perpendicular to the longitudinal direction in the heating zone of a tenter at a temperature of 100°C. Next, it was heat-set for 10 seconds at a temperature of 230°C in the heat treatment zone of the tenter. Then, after uniform slow cooling in the cooling zone, it was wound into a roll shape to obtain a laminated polyester film with layer X laminated on top.

[0133] Next, using a portion of the obtained laminated polyester film, coating agent A was applied by gravure coating to the surface of the laminated polyester film containing layer X that is opposite to the surface of layer X that is in contact with the polyester film, so that layer Y would have a thickness of 0.1 μm, thereby obtaining a laminated polyester film in which layers X and Y are laminated.

[0134] The release film using a laminated film having layer X when not stored in a humid, hot atmosphere, and the release film using a laminated film having layer X after being stored in a humid, hot atmosphere, exhibited excellent removal properties for layers X and Y, and were also excellent as release films.

[0135] (Example 22) A laminated polyester film was obtained by laminating layer X in the same manner as in Example 21, except that the thickness of layer X was changed as shown in the table, a polyester film in which layer X and layer Y were laminated, and a release film were obtained. The characteristics of each are shown in the table.

[0136] The release properties of layers X and Y in the laminated film having layer X when not stored in a humid, hot atmosphere, and in the release film having layer X after being stored in a humid, hot atmosphere, were at a level that posed no practical problems, and the film was suitable for use as a release film.

[0137] (Example 23) A laminated polyester film was obtained by laminating layer X in the same manner as in Example 22, except that the raw material for surface A was a mixture of 95 parts by mass of PET-1 and 5 parts by mass of MB-D, and the raw material for surface B was a mixture of 10 parts by mass of PET-1 and 90 parts by mass of MB-C. A polyester film in which layer X and layer Y were laminated, and a release film were obtained. The characteristics of each are shown in the table.

[0138] The release film using a laminated film having layer X when not stored in a humid, hot atmosphere, and the release film using a laminated film having layer X after being stored in a humid, hot atmosphere, exhibited excellent removal properties for layers X and Y, and were also excellent as release films.

[0139] (Example 24) In Example 21, adhesive Q was used as the release agent and applied by die coating to a thickness of 10 μm after drying. Subsequently, a release film roll for the process of releasing adhesive Q and removing the release agent was obtained from the resulting laminate. The film roll was introduced into a water washing apparatus equipped with an unwinding and winding device and washed with 60°C water for 2 minutes under a tension of 100 N / m to remove layers X and Y.

[0140] The release film using a laminated film having layer X when not stored in a humid, hot atmosphere, and the release film using a laminated film having layer X after being stored in a humid, hot atmosphere, exhibited excellent removal properties for layers X and Y, and were also excellent as release films.

[0141] (Example 25) As the raw material for side A, 95 parts by mass of PET-1 and 5 parts by mass of MB-D were mixed and vacuum-dried at 160°C for 2 hours. As the raw material for side B, 50 parts by mass of PET-1 and 50 parts by mass of MB-B were mixed and vacuum-dried at 160°C for 2 hours. Furthermore, as the raw material for the intermediate layer (layer C) between the layers constituting side A (layer A) and side B (layer B), PET-1 was vacuum-dried at 160°C for 2 hours. These materials were each fed into separate extruders, melted at 280°C, and laminated through a consolidation device in the order of layer A / layer C / layer B, with each layer having a thickness of 5 / 90 / 5. After lamination, the materials were extruded through a die onto a casting drum with a surface temperature of 25°C to produce an unstretched sheet. Subsequently, the sheet was preheated with a group of heated rolls, stretched 3.8 times in the longitudinal direction (MD direction) at a temperature of 90°C, and then cooled with a group of rolls at a temperature of 25°C to obtain a uniaxially oriented film. The obtained uniaxially oriented film was coated with coating agent F by bar coating so that the coating thickness after drying and stretching was 100 nm. Subsequently, while holding both ends of the film with clips, it was stretched 4.3 times in the width direction (TD direction) perpendicular to the longitudinal direction in a heating zone at 100°C inside a tenter. Next, it was heat-set for 10 seconds at a temperature of 230°C in the heat treatment zone inside the tenter. Then, after uniform slow cooling in the cooling zone, it was wound into a roll shape to obtain a laminated polyester film with layer X laminated on top.

[0142] Next, using a portion of the obtained laminated polyester film, coating agent A was applied by gravure coating to the surface of the laminated polyester film containing layer X that is opposite to the surface of layer X that is in contact with the polyester film, so that layer Y would have a thickness of 0.1 μm, thereby obtaining a laminated polyester film in which layers X and Y are laminated.

[0143] (Example 26) A laminated polyester film was obtained by laminating layer X in the same manner as in Example 21, except that coating agent M was used as layer X, a polyester film in which layer X and layer Y were laminated, and a release film.

[0144] (Reference example 1) The polyester film obtained in Example 21, from which layers X and Y were removed, was cut and fed into an extruder with vent holes. It was extruded at 280°C while maintaining a reduced pressure of 1 kPa or less to remove moisture, and processed into pellets to obtain recycled material-1. The glass transition temperature of the recycled material was 81°C, the melting point was 255°C, the intrinsic viscosity was 0.58, and the amount of terminal carboxyl groups was 28 eq. / t. The amount of components other than polyester in the recycled material was 0.47% by mass.

[0145] (Reference example 2) The polyester film obtained in Example 25, from which layers X and Y were removed, was cut and fed into an extruder with vent holes. It was extruded at 280°C while maintaining a reduced pressure of 1 kPa or less to remove moisture, and processed into pellets to obtain recycled material-2. The glass transition temperature of the recycled material was 81°C, the melting point was 255°C, the intrinsic viscosity was 0.58, and the amount of terminal carboxyl groups was 28 eq. / t. The amount of components other than polyester in the recycled material was 0.03% by mass.

[0146] (Example 27) A laminated polyester film was obtained by laminating layer X in the same manner as in Example 25, a polyester film in which layer X and layer Y are laminated, and a release film was obtained by mixing 95 parts by mass of PET-1 and 5 parts by mass of MB-D as raw materials for surface A and vacuum drying at 160°C for 2 hours, a raw material by mixing 50 parts by mass of PET-1 and 50 parts by mass of MB-B as raw materials for surface B and vacuum drying at 160°C for 2 hours, and a raw material by mixing 50 parts by mass of PET-1 and 50 parts by mass of recycled raw materials obtained in Reference Example 1 as raw materials for the intermediate layer (layer C) between the layer constituting surface A (layer A) and the layer constituting surface B (layer B) and vacuum drying at 160°C for 2 hours.

[0147] (Examples 28-30) A laminated polyester film was prepared in the same manner as in Example 21, except that coating agent K was used as layer X in Example 28, coating agent G in Example 29, and coating agent L in Example 30.

[0148] (Example 31) A raw material was obtained by mixing 85 parts by mass of PET-1, 5 parts by mass of MB-D, and 10 parts by mass of recycled raw material-1 obtained in Reference Example 1 as the raw material for surface A, and vacuum drying at 160°C for 2 hours. A raw material was obtained by mixing 50 parts by mass of PET-1 and 50 parts by mass of MB-B as the raw material for surface B, and vacuum drying at 160°C for 2 hours. Furthermore, a raw material was obtained by vacuum drying 100 parts by mass of PET-1 at 160°C for 2 hours as the raw material for the intermediate layer (layer C) between the layer constituting surface A (layer A) and the layer constituting surface B (layer B). A laminated polyester film was obtained by laminating layer X in the same manner as in Example 25, a polyester film in which layer X and layer Y are laminated, and a release film were obtained.

[0149] (Example 32) A raw material was obtained by mixing 85 parts by mass of PET-1, 5 parts by mass of MB-D, and 10 parts by mass of recycled raw material-1 obtained in Reference Example 1 as the raw material for surface A, and vacuum drying at 160°C for 2 hours. A raw material was obtained by mixing 10 parts by mass of PET-1, 40 parts by mass of MB-B, and 10 parts by mass of recycled raw material-1 obtained in Reference Example 1 as the raw material for surface B, and vacuum drying at 160°C for 2 hours. Furthermore, a raw material was obtained by vacuum drying 100 parts by mass of PET-1 at 160°C for 2 hours as the raw material for the intermediate layer (layer C) between the layer constituting surface A (layer A) and the layer constituting surface B (layer B). Using these materials, a laminated polyester film was obtained by laminating layer X in the same manner as in Example 25, a polyester film in which layer X and layer Y are laminated, and a release film were obtained.

[0150] (Example 33) A raw material was obtained by mixing 85 parts by mass of PET-1, 5 parts by mass of MB-D, and 10 parts by mass of recycled raw material-1 obtained in Reference Example 1 as the raw material for surface A, and vacuum drying at 160°C for 2 hours. A raw material was obtained by mixing 10 parts by mass of PET-1, 40 parts by mass of MB-B, and 10 parts by mass of recycled raw material-1 obtained in Reference Example 1 as the raw material for surface B, and vacuum drying at 160°C for 2 hours. Furthermore, a raw material was obtained by vacuum drying at 160°C for 2 hours using 50 parts by mass of PET-1 and 50 parts by mass of recycled raw material-1 obtained in Reference Example 1 as the raw material for the intermediate layer (layer C) between the layer constituting surface A (layer A) and the layer constituting surface B (layer B). Using these materials, a laminated polyester film was obtained by laminating layer X in the same manner as in Example 25, a polyester film in which layer X and layer Y are laminated, and a release film were obtained.

[0151] (Example 34) A raw material was obtained by mixing 85 parts by mass of PET-1, 5 parts by mass of MB-D, and 10 parts by mass of recycled raw material-1 obtained in Reference Example 1 as the raw material for surface A, and vacuum drying at 160°C for 2 hours. A raw material was obtained by mixing 50 parts by mass of PET-1 and 50 parts by mass of MB-B as the raw material for surface B, and vacuum drying at 160°C for 2 hours. Furthermore, a raw material was obtained by vacuum drying 100 parts by mass of PET-1 at 160°C for 2 hours as the raw material for the intermediate layer (layer C) between the layer constituting surface A (layer A) and the layer constituting surface B (layer B). A laminated polyester film was obtained by laminating layer X in the same manner as in Example 25, a polyester film in which layer X and layer Y are laminated, and a release film were obtained.

[0152] (Examples 35, 36) In Example 35, 95 parts by mass of PET-1 and 5 parts by mass of MB-D were used as raw materials for surfaces A and B, respectively. In Example 36, 30 parts by mass of PET-1 and 70 parts by mass of MB-C were used as raw materials for surfaces A and B, respectively. Except for these differences, a laminated polyester film with layer X laminated, a polyester film with layer X and layer Y laminated, and a release film were obtained in the same manner as in Example 19.

[0153] (Example 37) A laminated polyester film was obtained by laminating layer X in the same manner as in Example 21, except that a raw material was obtained by mixing 50 parts by mass of PET-1 and 50 parts by mass of MB-B as the raw material for surface A and vacuum drying at 160°C for 2 hours, and a raw material was obtained by mixing 95 parts by mass of PET-1 and 5 parts by mass of MB-D as the raw material for surface B and vacuum drying at 160°C for 2 hours. A polyester film in which layer X and layer Y were laminated was obtained. A release film was also obtained.

[0154] (Example 38) A coating agent F was applied to one side (side A) of Toray Industries, Inc.'s polyester film "Lumirror" (registered trademark) #50T60 using the gravure coating method so that the coating thickness after drying was 100 nm. The film was then wound into a roll shape to obtain a laminated polyester film with layer X.

[0155] Next, using a portion of the obtained laminated polyester film, coating agent A was applied using the gravure coating method to the side of the laminated polyester film opposite to the side of layer X that is in contact with the polyester film of layer X, so that layer Y would have a thickness of 0.1 μm, thereby obtaining a laminated polyester film in which layers X and Y are laminated. Note that the intrinsic viscosity after reuse was not measured.

[0156] (Example 39) A laminated polyester film was obtained by laminating layer X in the same manner as in Example 21, except that coating agent R was used as a component of layer X, a polyester film in which layer X and layer Y were laminated, and a release film.

[0157] (Example 40) As raw materials for layers A and B, 80 parts by mass of PET-1 and 20 parts by mass of MB-A were mixed, vacuum dried at 160°C for 2 hours, then fed into an extruder, melted at 280°C, and extruded through a die onto a casting drum with a surface temperature of 25°C to produce an unstretched sheet. Subsequently, the sheet was preheated with a group of heated rolls, then stretched 3.5 times in the longitudinal direction (MD direction) at 95°C, and then cooled with a group of rolls at 25°C to obtain a uniaxially oriented film. Coating agent S was applied to the obtained uniaxially oriented film by bar coating so that the coating thickness after drying would be 100 nm. Subsequently, while gripping both ends of the film with clips, it was stretched 3.7 times in the width direction (TD direction) perpendicular to the longitudinal direction in a heating zone at 95°C inside a tenter. Further, it was heat-set for 10 seconds at 220°C in a heat treatment zone inside the tenter. Next, after uniform slow cooling in a cooling zone, the material was wound up to obtain a laminated polyester film in which layer X was laminated.

[0158] A layer Y was obtained by applying coating agent A to the side of layer X of the obtained laminated polyester film that is opposite to the side in contact with the polyester film, using a gravure coating method, so that the thickness after drying is 100 nm.

[0159] A dielectric paste was applied to the obtained laminated polyester film by die coating to a thickness of 1.0 μm after drying, and 15 seconds after application, it was dried for 2 minutes in an oven at 100°C with an airflow of 5 m / s. Subsequently, the dielectric (release material) was released from the resulting laminate, and a film roll was obtained by winding up the laminated polyester film from which the release material had been removed. The film roll was introduced into a water washing device equipped with an unwinding and winding device, and washed with 100°C water for 2 minutes under a tension of 30 N / m to remove layers X and Y, and the polyester film was recovered.

[0160] (Example 41) A laminated polyester film with layer X laminated, a polyester film with layer X and layer Y laminated, and a release film were obtained in the same manner as in Example 21, except that the transverse stretching temperature was as shown in the table.

[0161] (Example 42) As the raw material for side A, 95 parts by mass of PET-1 and 5 parts by mass of MB-D were mixed and vacuum-dried at 160°C for 2 hours. As the raw material for side B, 50 parts by mass of PET-1 and 50 parts by mass of MB-B were mixed and vacuum-dried at 160°C for 2 hours. These raw materials were fed into separate extruders, melted at 280°C, and laminated through a consolidation device so that the thickness of the layer constituting side A (layer A) and the thickness of the layer constituting side B (layer B) were 5 / 95. The sheets were then extruded through a die onto a casting drum with a surface temperature of 25°C to produce an unstretched sheet. Subsequently, the sheet was preheated with a group of heated rolls, stretched 3.8 times in the longitudinal direction (MD direction) at a temperature of 90°C, and then cooled with a group of rolls at a temperature of 25°C to obtain a uniaxially oriented film. The obtained uniaxially oriented film was stretched 4.3 times in the width direction (TD direction) perpendicular to the longitudinal direction in a heating zone at 100°C inside a tenter, while both ends of the film were held with clips. Subsequently, it was heat-set for 10 seconds at a temperature of 230°C in the heat treatment zone inside the tenter. After uniform slow cooling in the cooling zone, it was wound into a roll shape to obtain a laminated polyester film without layer X.

[0162] A layer Y was applied to one side of a polyester film without layer X using a gravure coating method with coating agent D so that the thickness after drying was 0.1 μm, thereby obtaining a laminated polyester film with layer Y.

[0163] On the side of layer Y opposite to the side in contact with the polyester film, a dielectric paste was applied as a release agent by die coating to a thickness of 1.0 μm after drying. Subsequently, a release film roll for the process of releasing the dielectric and removing the release agent was obtained from the resulting laminate. This film roll was introduced into a water washing apparatus equipped with an unwinding and winding device, and washed with 60°C water for 2 minutes under a tension of 100 N / m to remove layer Y. Note that in Q. evaluation of the removeability of layers X and Y after moist heat treatment, coating agent D was used as layer Y instead of coating agent A for evaluation.

[0164] (Comparative Examples 1 and 2) Laminated polyester films were prepared in the same manner as in Example 1, except that PET-1 was used as the raw material for sides A and B, and coating agent N was used as layer X in Comparative Example 1, while coating agent O was used in Comparative Example 2. After laminating the release material, the film was peeled off, and then layers X and Y were removed to reuse the polyester film.

[0165] Comparative Example 1, in which the degree of saponification of the PVA constituting layer X is high, shows that the polar component γX of the surface free energy of layer X is P and hydrogen bonding component γX H Because the range was not favorable, the removal of layers X and Y was poor. Subsequently, when the crushed polyester film was melt-extruded according to item N above, layers X and Y could not be removed and remained, causing deterioration in the extruder and making it impossible to form a sheet.

[0166] Comparative Example 2, which has a large average degree of polymerization of the PVA constituting layer X, has a polar component γX of the surface free energy of layer X. P and hydrogen bonding component γX H Because the range was not favorable, the removal of layers X and Y was poor. Subsequently, when the crushed polyester film was melt-extruded according to item N above, layers X and Y could not be removed and remained, causing deterioration in the extruder and making it impossible to form a sheet.

[0167] (Comparative Example 3) A laminated polyester film was prepared in the same manner as in Example 42, except that coating agent A was used as layer Y. A ceramic green sheet and an adhesive sheet were laminated as release materials and evaluated. After peeling off the ceramic green sheet, layer Y was removed and the polyester film was reused.

[0168] Because layer X was absent and the HY(1)-HY(20)(°) of layer Y was not within the desirable range, the removal of layer Y was poor. Subsequently, when the crushed polyester film was melt-extruded according to item N above, layer Y could not be removed and remained, causing deterioration in the extruder and preventing the formation of a sheet.

[0169] [Table 1]

[0170] [Table 2]

[0171] [Table 3]

[0172] [Table 4]

[0173] [Table 5]

[0174] [Table 6]

[0175] [Table 7]

[0176]

Table 8

[0177]

Table 9

[0178]

Table 10

[0179]

Table 11

[0180]

Table 12

[0181]

Table 13

[0182]

Table 14

[0183]

Table 15

[0184] In addition, regarding the embodiments, if there are inconsistencies between the description in the specification and the description in the table, the description in the table shall prevail.

Industrial Applicability

[0185] The laminated polyester film of the present invention exhibits excellent solvent resistance during subsequent processes and excellent removal of layers other than the polyester film. Furthermore, by making layer Y of the present invention a water-repellent material, it can be suitably used as a release film for the manufacturing process of multilayer ceramic capacitors (MLCCs) using dielectric paste as the release material. In addition, since the polyester film can be easily recovered from the release film after use in the MLCC manufacturing process, the polyester film can be easily reused as a raw material for melt film formation.

Claims

1. A laminated polyester film having a polyester film and a layer X satisfying the following conditions: Condition 1: 20≦γX P ≦45 Condition 2: 3.0 ≦ γX H ≦10 γX P (mN / m): Polar component of surface free energy of layer X γX H (mN / m): Hydrogen bond component of the surface free energy of layer X

2. 2. The laminated polyester film according to claim 1, wherein the layer X contains a resin having a sulfonate-modified polyvinyl alcohol skeleton.

3. 3. The laminated polyester film according to claim 1 or 2, which has a layer Y, a layer X, and a polyester film, in that order, that satisfy the following conditions, and which is used for a release application in which a release layer is provided on the side of the layer Y opposite to the side that contacts the layer X, and the release layer is peeled off from the layer Y. Condition 9: 80≦HY(1)≦120 Condition 10: 1≦|HY(1)-HY(20)|≦90 HY(1) (°): Contact angle 1 second after water contacts layer Y HY(20) (°): Contact angle 20 seconds after water contacts layer Y

4. A method for producing a polyester film, comprising the steps of: using a laminated polyester film according to any one of claims 1 to 3, the polyester film comprising at least a release layer, a layer Y, the layer X, and recycled polyester raw material, in that order; peeling the release layer from layer Y; removing layer Y from the film from which the release layer has been peeled off; producing recycled raw material from the film from which the release layer and layer Y have been removed; and forming a film using the recycled raw material.

5. A method for producing a polyester film, comprising the steps of: using a laminated polyester film having at least a release layer, a layer Y satisfying the following conditions, and a polyester film containing recycled polyester raw materials, in that order; peeling the release layer from layer Y; removing layer Y from the film from which the release layer has been peeled off; producing recycled raw materials from the film from which the release layer and layer Y have been removed; and further forming a film using the recycled raw materials. Condition 9: 80≦HY(1)≦120 Condition 10: 1≦|HY(1)-HY(20)|≦90 HY(1) (°): Contact angle 1 second after water contacts layer Y HY(20) (°): Contact angle 20 seconds after water contacts layer Y

6. A laminated polyester film having a polyester film and a layer X, wherein the layer X contains a resin having a sulfonate-modified polyvinyl alcohol skeleton, the amount of copolymerization of the resin having a sulfonate-modified polyvinyl alcohol skeleton with a sulfonate is 0.1 mol % or more and 10 mol % or less, and when the average degree of polymerization of the layer X is determined according to the method specified in JIS K 6726 (1994), the determined average degree of polymerization is 200 or more and 2400 or less, and when the degree of saponification of the layer X is determined according to the method specified in JIS K 6726 (1994), the determined degree of saponification is 30 or more and 97 or less.

7. The laminated polyester film according to any one of claims 1 to 3 and 6, wherein layer X satisfies the following conditions: Condition 1': 20≦γX P≦41 Condition 2: 3.0≦γX H ≦10 γX P (mN / m): Polar component of the surface free energy of layer X γX H (mN / m): Hydrogen bond component of the surface free energy of layer X

8. The laminated polyester film according to any one of claims 1 to 3, 6 and 7, wherein the thickness xa (nm) of the layer X and the surface roughness RzjisB (nm) of the side (side B) opposite to the side (side A) having the layer X of the polyester film satisfy the following condition: Condition 3: 1.0≦RzjisB / xa≦20.0 xa (nm): thickness of layer X

9. 9. The laminated polyester film according to claim 1, wherein the thickness xa (nm) of the layer X and the surface roughness RzjisX (nm) of the layer X satisfy the following conditions: Condition 7: 0.01≦RzjisX / xa≦3.0

10. 10. The laminated polyester film according to claim 1, wherein the thickness xa of the layer X is 10 nm or more and 500 nm or less.

11. 11. The laminated polyester film according to claim 1, wherein the water contact angles HX(1) (°) and HX(20) (°) of the layer X satisfy the following condition: Condition 8: 5≦|HX(1)-HX(20)|≦60 HX(1)(°): Contact angle 1 second after water contacts layer X HX(20)(°): contact angle 20 seconds after water contacts layer X

12. 12. The laminated polyester film according to claim 1, wherein the layer X has a crystallinity of 14% or more and 40% or less.

13. 13. The laminated polyester film according to claim 12, wherein the crystallinity of the layer X is more than 31% and not more than 40%.

14. 14. The laminated polyester film according to claim 1, wherein the layer X contains a resin having a degree of polymerization of 200 or more.

15. A laminated polyester film as described in claim 3, characterized in that layer Y satisfies the following conditions: Condition 9': 100≦HY(1)≦110 Condition 10': 1≦|HY(1)-HY(20)|≦77 HY(1) (°): Contact angle 1 second after water contacts layer Y HY(20) (°): Contact angle 20 seconds after water contacts layer Y

16. 16. The laminated polyester film according to claim 3, wherein the surface of the layer Y has a solvent resistance of 5% to 100% as determined by the following method. [Method for measuring solvent durability] Testing machine: Gakushin type testing machine (type II friction testing machine described in JIS L 0849 (2013)) Friction element: Cotton cloth (No. 3 gold cloth) soaked in a mixed solvent of toluene and ethanol (mass ratio 1:1) Load capacity: 1kg Number of trips: 30 round trips Solvent durability rate (%) = F(A) / F(B) x 100 F(A): Peel force of layer Y surface F(B): Peel strength of layer Y surface after solvent-impregnated cloth rubbing test

17. The hydrogen bond component γ of the surface free energy of the layer Y H 17. The laminated polyester film according to claim 3, 15 or 16, wherein the value of the linear modulus is 1.5 or more and 10 or less.

18. 18. The laminated polyester film according to claim 3, which is used in an application in which the layer X and the layer Y are removed after the release layer is peeled off from the layer Y.

19. 20. The laminated polyester film according to claim 18, which is used for reusing the laminated polyester film from which the layer X and the layer Y have been removed.

20. 20. The laminated polyester film according to claim 3, wherein the release layer is a ceramic green sheet containing barium titanate as a main component.

21. A method for producing a polyester film as described in claim 4 or 5, wherein the polyester film containing the recycled polyester raw material has a laminated structure of three or more layers, including a layer (A layer) that constitutes side A, which is one surface of the polyester film, a layer (B layer) that constitutes side B, which is the other surface, and a layer (C layer) that has no surface.

22. A method for producing a polyester film as described in claim 21, wherein the polyester film containing recycled polyester raw materials contains recycled polyester raw materials in the C layer.